Asian interior humidity variations through the last glacial cycle: dominant effect of westerly jet displacement - Wanxin Liu; Zhaoxia Jiang; Andrew P. Roberts; Chunqing Sun; Sanzhong Li; Yulong Guan; Liang Zhou (Quaternary Science Reviews, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Serpentinization in Jezero crater: Comparing SuperCam Mars data to terrestrial serpentinites - J.M. Comellas; S.K. Sharma; P.J. Gasda; A. Cousin; A. Essunfeld; P. Fryer; L.E. Mayhew; L. Sun; A.J. Brown; T.E. Acosta-Maeda; E. Dehouck; M. Veneranda; et al. (Icarus, 2026)

Longitudinal blood pressure changes in relation to urinary toxic/essential metals and metal mixtures - Margaret C. Weiss; Jiehuan Sun; Brian P. Jackson; Mary E. Turyk; Luyu Wang; Eric L. Brown; David Aguilar; Sharon A. Brown; Craig L. Hanis; Maria Argos; Robert M. Sargis (Environmental Research, 2026)

Advancements in isotopic signatures, source tracking, and abiotic transformation pathways of glyphosate: A critical review of environmental fate and risk mitigation - Hui Li; Spencer R. Moller; Deb P. Jaisi; Mingjing Sun (Critical Reviews in Environmental Science and Technology, 2026)

Consequential life cycle assessment of European livestock systems: current practices, limitations, and priorities - Dengsheng Sun; Marie Trydeman Knudsen; Thomas Ponsioen; Ricardo Teixeira; Alina Chervinska; Mariana Raposo; Rahela Lucić; Mali Gravell; Nicholas Davison; Lewis Cameron; Sally Westaway; Aurélie Wilfart; et al. (Journal of Industrial Ecology, 2026)
A systems-level understanding of livestock production and its environmental consequences is essential for informing sustainability transitions and evidence-based policy in Europe. While life cycle assessment (LCA) is widely applied in this context, the use of consequential LCA (CLCA), which aims to capture market-mediated and structural system responses, remains comparatively limited. This study provides a critical synthesis of CLCA applications in European livestock systems through a PRISMA-guided systematic literature review complemented by an expert workshop. Twenty-three studies met the inclusion criteria, spanning multiple livestock groups, regions, and modelling approaches. Scenario development was dominated by technical or management-oriented adjustments, with limited use of optimisation-based, narrative, or policy-driven frameworks capable of exploring transformative system changes. Inventory construction typically relied on Ecoinvent, supplemented where necessary by experimental datasets, expert elicitation, survey data, or outputs from economic models. Most studies focused on midpoint indicators, and although uncertainty analysis was commonly included, its implementation was inconsistent across studies. Overall, most of the reviewed CLCA applications remain focused on incremental improvements within existing systems, limiting their ability to assess the consequences of more profound system transitions. Key limitations include both methodological challenges (particularly in scenario formulation and the representation of system-wide responses) and data gaps, notably the limited availability of regionally specific inventory data for marginal processes and endpoint characterisation factors. We recommend that future CLCAs adopt more structured and forward-looking scenario development approaches, strengthen inventory construction through updated and localised datasets, and consider the incorporation of both midpoint and endpoint indicators, while clearly acknowledging the limitations of both approaches. In addition, the systematic application of sensitivity and scenario-based uncertainty analysis is essential for assessing robustness. Addressing these practical and methodological dimensions will enhance the contribution of CLCA to analysing sustainability transitions of European livestock systems.

Retraction notice to “Toxicity of perfluorobutanesulfonate on gill functions of marine medaka (Oryzias melastigma): A time course and hypoxia co-exposure study” [Sci. Total Environ. 872 (2023) 162297] - Baili Sun; Jing Li; Chenyan Hu; John P. Giesy; Paul K.S. Lam; Lianguo Chen (Science of The Total Environment, 2026)

Liquified SO2 induced solid/cathode electrolyte interphase for lithium ion batteries - Bishnu P. Thapaliya; Xiao-Guang Sun; Albina Y. Borisevich; Harry M. Meyer; Sheng Dai (Chemical Engineering Journal, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Co-evolution of marine ecosystems and nutrient cycles during the Great Ordovician Biodiversification Event - Shengchao Yang; Thomas J. Algeo; Thomas Servais; Ronald E. Martin; David A.T. Harper; Charles R. Marshall; Yiying Deng; Zongyuan Sun; Zhengbo Lu; Jian Cao; Chao Li; Shu-zhong Shen; et al. (Earth and Planetary Science Letters, 2026)

Blood and lymphatic vascular network in bone injury repair: from molecular mechanisms to therapeutic strategies - Minghan Ye; Nanjing Li; He Cai; Yixin Shi; Haiyang Sun; Anjali P. Kusumbe; Junyu Chen (Science China Life Sciences, 2026)

Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Cyclic shear behavior of concrete columns with debonded and low-bond high-strength rebars - J. H. Wang; Y. J. Lv; Q. Wu; Y. P. Sun (Bulletin of Earthquake Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Organic matter supply triggers rapid microbial-driven changes in carbon-nitrogen cycling in subterranean estuary sediments - Danqing Sun; Longyun Lai; Yueming Wu; Ying Wu; Jian Li; J. Severino P. Ibánhez; Shan Jiang (Marine Chemistry, 2026)

¡Mi Vida Saludable!: Results of a Randomized, Controlled, 2 × 2 Factorial Trial of an In-Person and eHealth Diet and Physical Activity Intervention in Latina Breast Cancer Survivors - Heather Greenlee; Margarita Santiago-Torres; Isobel Contento; Pamela A. Koch; Eileen Rillamas-Sun; Heewon L. Gray; Adam M. Brickman; Ann Ogden Gaffney; Cynthia A. Thomson; Tracy E. Crane; Naxielly Dominguez; Jhack Sepulveda; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Polysaccharide lyase family 3 subfamily 2 is specific for highly methyl-esterified homogalacturonan characterized for two Aspergillus nidulans lyases - Nan Zhang; Jan Willem Zwolschen; Mao Peng; Giovanni van Kralingen; Gijs J.C. Vreeke; Henk A. Schols; Ronald P. de Vries; Peicheng Sun; Mirjam A. Kabel (Carbohydrate Polymers, 2026)

Genetic improvement of nitrogen- and phosphorus-use efficiency in crops: Old goals with new aspirations - Wei Wang; Da Chen; Huwei Sun; Surya Kant; John P. Hammond; Lei Shi; Chengcai Chu (Molecular Plant, 2026)

In-situ fabrication of magnetic nanoparticle-decorated rGO/TiO2@MXene aerogels for enhanced visible-light-driven degradation of organic pollutants - Rushikesh P. Dhavale; Varsha D. Phadtare; Sagar A. Chaudhari; Mukund G. Mali; Vinayak G. Parale; Santosh V. Mohite; Donghwa Lee; Haryeong Choi; Akshay A. Ransing; Jiseung Kim; Sun Hee Kim; Prashant B. Patil; et al. (Journal of Water Process Engineering, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Non-linear interaction behavior of mixed industrial solid wastes in circulating fluidized beds: Reacting MP-PIC simulation - Minmin Zhou; Xiuzhi Wang; WenQiang Chen; Qiuchen Sun; DongFu Wang; Zhijiang Han; Chenxi Lu; Yueming Wang; Lunbo Duan; Wojciech P. Adamczyk (Fuel, 2026)

Projection of fire weather index in Daxing’anling, Northeast China using a machine learning-based CMIP6 multi-model ensemble - Stephane G. P. Debulois; Min Sun; Mingshi Li (Climatic Change, 2026)

Enzymatic production of prebiotic xylooligosaccharides - Lucas F. Almeida; Lanyu Li; Ronald P. de Vries; Peicheng Sun; Gabriela Piccolo Maitan-Alfenas (World Journal of Microbiology and Biotechnology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Emergent constraints reveal underprediction of future global water availability under anthropogenic forcing - Senlin Tang; Qiang Zhang; Xintong Gong; Chong-Yu Xu; Vijay P. Singh; Fubao Sun; Yao Feng; Ziwei Li; Likun Han (Global and Planetary Change, 2026)

Quantitative analysis of temperature-dependent transition of CO2 adsorption mechanisms by adsorbents – From enthalpy-driven interactions to pore-filling capture - Kaijie Xuan; Jie Wu; Yifan Zhang; Longchun Zhong; Rashid M. Othman; George P. Lithoxoos; Faiz Almansour; Ali Nabeeh Shakhs; Jiawei Wang; Xin Sun; Wei-Ping Pan (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Contrasting responses of soil organic and inorganic carbon to manure addition in calcareous soil - Yunlong Zhang; Lei Liu; Dongdong Luan; Zhou Jia; Iain P. Hartley; Muxi Xie; Xinhe Shan; Jiangzhou Zhang; Shiyou Sun; Ling Wang; Junling Zhang (Soil and Tillage Research, 2026)

Estimation of CO2 storage capacities in saline sandstone aquifers using material balance considering CO2 dissolution trapping - Yeongju Kim; Sangkeon Park; Hunjoo P. Lee; Wenyue Sun; Hisanao Ouchi; Hoonyoung Jeong (Fuel, 2026)

Nanopore structure characterization of Velkerri Shale: SANS investigation of pore accessibility and anisotropy - Yeping Ji; Mihaela Grigore; Andrzej P. Radlinski; Claudio Delle Piane; Tomasz Blach; Xiao Chen; Phung Vu; Mengdi Sun; Richard Sakurovs; Liliana de Campo; Elliot P. Gilbert; Klaus Regenauer-Lieb (Fuel, 2026)

Building occupancy detection using thermal imaging based edge computing - Navian Francis; Ryan P. Wood; Rutuja Shivarkar; Ye Sun (Building and Environment, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Mechanisms driving the global tropical response to a weakened AMOC during Heinrich Stadial 1 - A.E. Lawman; C. Sun; X. Wu; T. Sun; N. Piatrunia; K. Gomez; M. Kageyama; U. Merkel; M. Prange; B. Otto-Bliesner; X. Zhang; P. DiNezio; et al. (Quaternary Science Reviews, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

Radiofrequency electromagnetic heating enhanced vitrification of viable large cartilage tissues - Haiyang Ma; Josh Wewerk; Ge Pan; A.J. Riffe; Peng Chen; Yaqian Sun; John M. Alford; Kristi Helke; Girish Srinivas; Hai Yao; David P. Eisenberg; Shangping Wang (Cryobiology, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

Personalized Environmental Control Systems (PECS): Systematic review of benefits for thermal comfort, air quality, health, and human performance - Dolaana Khovalyg; Mariya P. Bivolarova; Jun Shinoda; Douaa Al-Assaad; Marika Vellei; Karol Bandurski; Giorgia Chinazzo; Ongun B. Kazanci; Joyce Kim; Tobias Kramer; Aleksandra Lipczynska; Shichao Liu; et al. (Building and Environment, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

A Genomic Exploration of the Possible De‐Extirpation of the Zanzibar Leopard - Xin Sun; Emily Louisa Cavill; Ashot Margaryan; Jianqing Lin; Søren Thingaard; Tamrini A. Said; Shyam Gopalakrishnan; M. Thomas P. Gilbert (Molecular Ecology, 2025)
The recently extirpated Zanzibar leopard was the only known African leopard ( Panthera pardus spp.) population restricted exclusively to a major island habitat. Although its demise was driven through habitat change and conflict with humans, given its role as a keystone species for the Zanzibar Archipelago, its successful potential reintroduction might offer a means for helping preserve the natural biodiversity of its former habitat. Whether this is feasible, however, would be contingent on both whether closely related source populations can be identified on mainland Africa, and whether the Zanzibar form exhibited any special adaptations that might need to be considered when choosing such a source. In light of these questions, we genomically profiled two of the six known historic specimens, to explore whether they represent a realistic candidate for de‐extirpation through reintroduction. Our analyses indicate that despite its geographical separation, the Zanzibar leopard shared a close genetic relationship with mainland East African individuals. Furthermore, although its uniqueness as an island population was emphasised by genomic signatures of high inbreeding and increased mutation load, the latter similar to the level of the critically endangered Amur leopard ( P. p. orientalis ), we find no evidence of functionally significant genetic diversity unique to Zanzibar. We therefore conclude that should attempts to restore leopards to Zanzibar be considered, then mainland East African leopards would provide a suitable gene pool.

Nitroquinolones and nitroquinolines: syntheses and antitrypanosomal activity - Phelelisiwe S. Dube; Karol R. Francisco; Lesetja J. Legoabe; Yujie Uli Sun; Yashpreet Kaur; Tina P. Nguyen; Conor R. Caffrey; Richard M. Beteck (Molecular Diversity, 2025)

Oxidative cleavage of methyl-esterified pectic homogalacturonan by an AA17 lytic polysaccharide monooxygenase from Phytophthora infestans - Peicheng Sun; Mao Peng; Florian Csarman; Astrid Müller; Nan Zhang; Willem J.H. van Berkel; Roland Ludwig; Ronald P. de Vries; Mirjam A. Kabel (Carbohydrate Polymers, 2025)

Compound drought-heatwaves in China: driving factors and risks - Anlan Feng; Qiang Zhang; Xihui Gu; Vijay P. Singh; Lei Hu; Yixin Sun; Jiaqi Zhao (Natural Hazards, 2025)

Longer WIC Participation Is Associated With Higher Diet Quality and Consumption of WIC-Eligible Foods Among Children 2-5 Years Old - Lauren E. Au; Hannah R. Thompson; Lorrene D. Ritchie; Brenda Sun; Thea P. Zimmerman; Shannon E. Whaley; Amanda Reat; Kavitha Sankavaram; Christine Borger (Journal of the Academy of Nutrition and Dietetics, 2025)

Subduction-driven mantle melting controls the magmatic evolution of the early Permian Tianshan orogen - Xiangsong Wang; Shengxuan Tang; Kai Wang; Keda Cai; Min Sun; Guochun Zhao; Ian P. Cawood (Global and Planetary Change, 2025)

Molecular insights into Yb(III) speciation in sulfate-bearing hydrothermal fluids from X-ray absorption spectra informed by ab initio molecular dynamics - Xiaodong Zhao; Duo Song; Sebastian T. Mergelsberg; Micah P. Prange; Daria Boglaienko; Zihua Zhu; Zheming Wang; Carolyn I. Pearce; Chengjun Sun; Kevin M. Rosso; Xiaofeng Guo; Xin Zhang (Geochimica et Cosmochimica Acta, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

Fast hydrothermal and microwave synthesis of high purity methylated imogolite nanotubes - Y. Zhang; F. Alfadel Raad; P. Picot; F. Gobeaux; A. Thill; X. Sun; D. Schaming; L. Sicard (Applied Clay Science, 2025)

PP2A attenuates α-amanitin-induced liver injury by promoting autophagy and inhibiting apoptosis in mouse models - Hui Xu; Jian Sun; Yu Zhao; Yaxiong Zhou; Kuan Wang; Xiang Liu; Jieyan Yang; Peng Wu; Shengkui Wang; John P. Kastelic; Weijie Qu; Limei Zhang; et al. (Chemico-Biological Interactions, 2025)

Physics informed neural network for forward and inverse multispecies contaminant transport with variable parameters - Qingzhi Hou; Xiaolong Xu; Zewei Sun; Jianping Wang; Vijay P. Singh (Journal of Hydrology, 2025)

Procedural Variation May Contribute to 6-Minute Walk Distance Variability in Real-World Pediatric Pulmonary Arterial Hypertension Study - Cynthia Kleppinger; Dunbar Ivy; Norman Stockbridge; Angela Bates; Stephanie Handler; Usha S. Krishnan; Mary P. Mullen; Delphine Yung; Rachel K. Hopper; Nidhy P. Varghese; Jeff Fineman; Eric D. Austin; et al. (The AAPS Journal, 2025)
The six-minute walk test (6MWT) is a common method to assess submaximal exercise capacity in children and adults with pulmonary arterial hypertension (PAH) and other chronic diseases. There is no guideline specifically for 6MWT in children. In this observational pilot study, we evaluated the impact of procedural variations on the outcome of the 6MWT in the real-world clinical setting at pediatric PAH programs. We collected 6MWT data from 33 children with PAH participating in a multicenter, prospective, non-interventional study. Data range/quantiles and standard deviation (SD) were used to describe distribution of the six-minute walk distance (6MWD) and data variability. Levene’s test was used to test for heterogeneity of variance with the two sites of similar altitude and their age/height/weight-matched Panama Function Class II participants. We analyzed all 33 eligible participants and their qualified first walks at five centers (A-E) with 6MWD ranges of 420–570, 357–683, 418–481, 400–700, 377–549 m, respectively. Site D performed the 6MWT in a busy hallway and allowed parental/caregiver’s cheering, while Site E performed the 6MWT in a secluded area with no parental/caregiver involvement. Mean 6MWD and SD for Sites D and E were 547 (125) and 432 (67.5) meters, respectively (p = 0.03). In conclusion, procedural variations seem to associate with 6MWD data variability. Although interpretation of our results is limited by the small sample size, our findings suggest that standardizing pediatric 6MWT procedures are needed. Graphical Abstract

Additive-assisted passivating by 2-(2,2,2-trifluoroethoxy)aniline and semitransparent perovskite solar cells fabricated by thermocompression - Bo Shen; Qingqing Zhou; Qing Sun; Bonan Kang; S. Ravi P. Silva (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Identification and influence of soil type and urea foliar application on phenolic compounds in the red musts and wines of Tempranillo variety - Jiarong Zhang; Eva P. Pérez-Álvarez; Pinhe Liu; Rebeca Murillo-Peña; Matteo Bordiga; Xuequan Sun; Monica Locatelli; Jean Daniel Coïsson; José M. Martínez-Vidaurre; Harold Corke; Teresa Garde-Cerdán (Food and Humanity, 2025)

Urbanization has enhanced compound heatwaves - Peng Sun; Shifang Yu; Rui Yao; Zhongbao Sun; Vijay P. Singh; Yaojin Bian; Chenhao Ge; Qiang Zhang (Journal of Geographical Sciences, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Conodonts suggest a late Spathian (late Early Triassic) age for Thaisaurus chonglakmanii (Reptilia: Ichthyosauromorpha) from Thailand - Si-Yao Ye; Kui Wu; Zuo-Yu Sun; P. Martin Sander; Adun Samathi; Yuan-Yuan Sun; Cheng Ji; Varavudh Suteethorn; Jun Liu (Palaeoworld, 2025)

Eco-hydrological recovery following large vegetation disturbances from a mega earthquake on the eastern Tibetan plateau - Jiehao Zhang; Yulong Zhang; Matthew P. Dannenberg; Qinfeng Guo; Jeff W. Atkins; Wenhong Li; Ge Sun (Journal of Hydrology, 2025)

Does root respiration and root anatomical traits affect crop yield under stress? A meta-analysis and experimental study - Pengzhen Du; Jonathan P. Lynch; Zhengli Sun; Feng-Min Li (Plant and Soil, 2025)

Assessing predictions on fitness effects of missense variants in HMBS in CAGI6 - Jing Zhang; Lisa Kinch; Panagiotis Katsonis; Olivier Lichtarge; Milind Jagota; Yun S. Song; Yuanfei Sun; Yang Shen; Nurdan Kuru; Onur Dereli; Ogun Adebali; Muttaqi Ahmad Alladin; et al. (Human Genetics, 2025)

Correction: Axial-shear-flexure interactive behavior and completed shear strength model of reinforced concrete members considering steel-bond slip - J. H. Wang; Y. P. Sun (Bulletin of Earthquake Engineering, 2025)

Axial-shear-flexure interactive behavior and completed shear strength model of reinforced concrete members considering steel-bond slip - J. H. Wang; Y. P. Sun (Bulletin of Earthquake Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High-temperature ammonia treatment of zeolite-template carbon for enhanced CO2 adsorption: A study on diffusion behaviors and adsorption mechanisms - Yifan Zhang; Xifeng Zhu; Jiaxin Wang; Longchun Zhong; Rashid M.Othman; George P. Lithoxoos; Ali Nabeeh Shakhs; Faiz Almansour; Xi Zeng; Xin Sun; Wei-Ping Pan (Chemical Engineering Journal, 2025)

Effects of igneous contact metamorphism on the mineral and toxic trace element composition of low-sulfur coal in the Huaibei Coalfield, eastern China - Bingxiang Liu; Xiaopeng Song; Ning Wang; Victor P. Nechaev; Qingli Zhu; Bowen Zhang; Shuhao Tang; Ruoyu Sun (Applied Geochemistry, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Carbon Policies and Liner Speed Optimization: Comparisons of Carbon Trading and Carbon Tax Combined with the European Union Emissions Trading Scheme - Ming Sun; Midakpe P. Vortia; Guangnian Xiao; Jing Yang (Journal of Marine Science and Engineering, 2025)
This paper explores how optimizing vessel speeds can help reduce carbon emissions in the maritime industry. Focusing on liner shipping routes between China and Europe, it examines how carbon pricing mechanisms, including carbon taxes and emissions trading under the European Union Emissions Trading Scheme (EU ETS), impact operational costs and emissions reduction. With the use of advanced optimization methods, such as the Non-dominated Sorting Genetic Algorithm-II (NSGA-II) and the Technique for Order of Preference by Similarity to an Ideal Solution (TOPSIS), this research explores the balance between adjusting vessel speeds and minimizing emissions. The findings show that shipping companies on the China–Europe route can reduce the financial strain of carbon pricing by carefully managing speeds and voyage times. This study compares two scenarios of carbon tax policy and carbon trading rights in terms of voyage costs and carbon emissions. The results of this comparison based on the given parameters indicate a reduction of 1124 tons of carbon emissions with the carbon tax policy scenario, while the carbon trading rights scenario allows for more voyages yearly (5.24 vs. 5.30). This demonstrates one policy being more economical, while the other is also more environmentally efficient. These insights support the development of strategies that align environmental goals with economic priorities, paving the way for more sustainable maritime operations. The study introduces its objectives and reviews relevant literature by presenting a detailed methodology, incorporating emissions modeling with clearly defined parameters. The analysis presents results that undergo sensitivity testing and limitations using MATLAB (R2022a version). The study concludes by discussing policy implications and recommendations for future research and practical advancement

Real collapse responses of an RC flat plate structure under extreme overloading condition: Reversing load redistribution - Zhi Yang; Xuekang Guo; Yi Li; Hong Guan; Mengzhu Diao; Benoit P. Gilbert; Hailin Sun (Engineering Structures, 2025)

Hydrological responses of three gorges reservoir region (China) to climate and land use and land cover changes - Yixin Sun; Qiang Zhang; Wenlong Song; Senlin Tang; Vijay P. Singh (Natural Hazards, 2025)

Putting seedlings on the map: Trade‐offs in demographic rates between ontogenetic size classes in five tropical forests - Stephan Kambach; Helge Bruelheide; Liza S. Comita; Richard Condit; S. Joseph Wright; Salomón Aguilar; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; Nancy C. Garwood; Stephen P. Hubbell; Pei‐Jen Luo; Margaret R. Metz; et al. (Ecology, 2025)
All species must partition resources among the processes that underly growth, survival, and reproduction. The resulting demographic trade‐offs constrain the range of viable life‐history strategies and are hypothesized to promote local coexistence. Tropical forests pose ideal systems to study demographic trade‐offs as they have a high diversity of coexisting tree species whose life‐history strategies tend to align along two orthogonal axes of variation: a growth–survival trade‐off that separates species with fast growth from species with high survival and a stature–recruitment trade‐off that separates species that achieve large stature from species with high recruitment. As these trade‐offs have typically been explored for trees ≥1 cm dbh, it is unclear how species' growth and survival during earliest seedling stages are related to the trade‐offs for trees ≥1 cm dbh. Here, we used principal components and correlation analyses to (1) determine the main demographic trade‐offs among seed‐to‐seedling transition rates and growth and survival rates from the seedling to overstory size classes of 1188 tree species from large‐scale forest dynamics plots in Panama, Puerto Rico, Ecuador, Taiwan, and Malaysia and (2) quantify the predictive power of maximum dbh, wood density, seed mass, and specific leaf area for species' position along these demographic trade‐off gradients. In four out of five forests, the growth–survival trade‐off was the most important demographic trade‐off and encompassed growth and survival of both seedlings and trees ≥1 cm dbh. The second most important trade‐off separated species with relatively fast growth and high survival at the seedling stage from species with relatively fast growth and high survival ≥1 cm dbh. The relationship between seed‐to‐seedling transition rates and these two trade‐off aces differed between sites. All four traits were significant predictors for species' position along the two trade‐off gradients, albeit with varying importance. We concluded that, after accounting for the species' position along the growth–survival trade‐off, tree species tend to trade off growth and survival at the seedling with later life stages. This ontogenetic trade‐off offers a mechanistic explanation for the stature–recruitment trade‐off that constitutes an additional ontogenetic dimension of life‐history variation in species‐rich ecosystems.

Investigation of inter-subject variation in ultrafine particle deposition across human nasal airways: A study involving children, adults, and the elderly - Qinyuan Sun; Ya Zhang; Lin Tian; Jiyuan Tu; Richard Corley; Andrew P. Kuprat; Jingliang Dong (Science of The Total Environment, 2024)

Microwave-assisted CuO-modified porous ZnO nanosheet for photocatalytic degradation of organic pollutants and antibacterial inactivation - Min Seok Song; Ruturaj P. Patil; Mahadeo A. Mahadik; You Jin Jo; Jung-Hee Park; Weon-Sik Chae; Sun Hee Choi; Hyun Hwi Lee; Jum Suk Jang (Journal of Environmental Chemical Engineering, 2024)

PLMC: Language Model of Protein Sequences Enhances Protein Crystallization Prediction - Dapeng Xiong; Kaicheng U; Jianfeng Sun; Adam P. Cribbs (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Native and invaded-range surveys provide mixed support for enemy-release of Nymphoides peltata in the invaded range - Nathan E. Harms; Matthew Purcell; Sun-hee Hong; Sonja Stutz; Jialiang Zhang; Megann Harlow; Chenxi Liu; Nicholas P. Tippery (Aquatic Botany, 2024)

Diffusion mechanism of C-S grout with time-varying viscosity in inclined rock fissure under seawater conditions - P. Li; C. Q. Wang; Y. Liu; L. Y. He; X. Y. Liu; H. H. Zhao; Y. Sun (Marine Georesources & Geotechnology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Risk assessment of high maturity lacustrine shale oil reservoir based on pore-fracture connectivity and decane accessibility, Ordos Basin (China) - Jianjiang Wen; Mengdi Sun; Bingsong Yu; Mehdi Ostadhassan; Tomasz P. Blach; Yeping Ji; Phung Vu; Liliana de Campo; Chunming Wu; Jingfu Mu; Zijie Ren; Xin Tian; et al. (Marine and Petroleum Geology, 2024)

LP-46 Leaky gut causes inflammatory stress: a determinant of acute liver injury induced by coadministration of rhein and LPS - L. Gong; P. Liu; D. Hu; J. Xu; X. Li; Y. Long; J. Chen; J. Sun (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Acceleration of bulk and surface charger transfer dynamics via FePi cocatalyst-coated Ti/(Sb)-Fe2O3:Sb/(Ti)-Fe2O3 type-II homojunction photoanode for photoelectrochemical performance - Periyasamy Anushkkaran; Ruturaj P. Patil; Weon-Sik Chae; Manish Kumar; Sun Hee Choi; Hyun Hwi Lee; Hyun Gyu Kim; Bong-Kyu Kim; Jum Suk Jang (Chemical Engineering Journal, 2024)

Experimental and numerical investigation of punching and post-punching shear capacities of post-tensioned flat plate slab-column joints influenced by prestressing levels - Ziyang Jiao; Yi Li; Hong Guan; Mengzhu Diao; Hailin Sun; Ziqi Zhao; Benoit P. Gilbert (Engineering Structures, 2024)

Comparison of Fatigue Hydraulic Fracturing of Granite Cores Subjected to Creep and Cyclic Injection - Li Zhuang; Changlun Sun; Hannes Hofmann; Arno Zang; Günter Zimmermann; Linmao Xie; Guanyi Lu; Andrew P. Bunger (Rock Mechanics and Rock Engineering, 2024)

Intelligent salivary biosensors for periodontitis: in vitro simulation of oral oxidative stress conditions - Haritha George; Yani Sun; Junyi Wu; Yan Yan; Rong Wang; Russell P. Pesavento; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2024)

An improved corresponding states principle model for orthohydrogen thermal conductivity from the triple point to 300 K and 20 MPa - Chuiju Meng; Jiadong Sun; Yilun Yang; Huashan Bao; Anthony P. Roskilly; Yonghua Huang (International Journal of Refrigeration, 2024)

Multiresponsive luminescent metal–organic framework for cooking oil adulteration detection and gallium(III) sensing - Dmitry I. Pavlov; Xiaolin Yu; Alexey A. Ryadun; Denis G. Samsonenko; Pavel V. Dorovatovskii; Vladimir A. Lazarenko; Na Sun; Yaguang Sun; Vladimir P. Fedin; Andrei S. Potapov (Food Chemistry, 2024)

Physics-informed neural network for diffusive wave model - Qingzhi Hou; Yixin Li; Vijay P. Singh; Zewei Sun (Journal of Hydrology, 2024)

Nitric oxide-mediated regulation of Aspergillus flavus asexual development by targeting TCA cycle and mitochondrial function - Kunlong Yang; Yue Luo; Tongzheng Sun; Han Qiu; Qingru Geng; Yongxin Li; Man Liu; Nancy P. Keller; Fengqin Song; Jun Tian (Journal of Hazardous Materials, 2024)

Characterization of Fusarium species causing head blight of highland barley (qingke) in Tibet, China - Sun Fuyao; Zhang Tangwei; Xing Yujun; Dai Chengcheng; Ciren Deji; Yang Xiaojun; Wu Xuelian; P. Mokoena Mduduzi; O. Olaniran Ademola; Shi Jianrong; Ma Changzhong; Xu Jianhong; et al. (International Journal of Food Microbiology, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

Paleoecology and paleobiogeography of the latest Miocene site of Shuitangba, Zhaotong, China - D.F. Su; J. Kelley; L.J. Flynn; X.P. Ji; C.L. Deng; T. Deng; P. Li; Z. Li; W.J. Sanders; T.A. Stidham; F. Sun; X. Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Effects of Bulleyaconitine A on Extracellular Matrix Secretion and Expression of Related Proteins in Acetaldehyde-Activated Hepatic Stellate Cells - Q. W. Song; Y. P. Yuan; Q. S. Sun; X. D. Zhan; Y. X. Jiang; X. N. Tang (Bulletin of Experimental Biology and Medicine, 2024)

Physics-informed neural network for solution of forward and inverse kinematic wave problems - Qingzhi Hou; Yixin Li; Vijay P. Singh; Zewei Sun; Jianguo Wei (Journal of Hydrology, 2024)

Development of a nonstationary Standardized Precipitation Evapotranspiration Index (NSPEI) and its application across China - Peng Sun; Chenhao Ge; Rui Yao; Yaojin Bian; Huilin Yang; Qiang Zhang; Chong-Yu Xu; Vijay P. Singh (Atmospheric Research, 2024)

Effects of coexisted substances on the separation characteristics and mechanisms of perfluorooctanoic acid by polyamide composite nanofiltration membrane - Z. Liu; J. J. Guo; J. X. Wang; Y. N. Hu; X. L. Yue; P. D. Sun; Y. S. Hou; J. Q. Duan; L. Wang; N. Wang; T. Liang (International Journal of Environmental Science and Technology, 2024)

Confinement effect in nanopores of shale and coal reservoirs: A review on experimental characterization methods - Minghan Li; Mengdi Sun; Erfan Mohammadian; Yeping Ji; Tomasz P. Blach; Mehdi Ostadhassan; Jianjiang Wen; Chunming Wu; Zhejun Pan (Gas Science and Engineering, 2024)

Insights into progress of wheat breeding in arid and infertile areas of China in the last 14 years - Long Li; Jingyi Wang; Chaonan Li; Xinguo Mao; Xiaoqing Zhang; Junwei Sun; Ke Zhang; Yuping Liu; Matthew P. Reynolds; Ziguang Yang; Ruilian Jing (Field Crops Research, 2024)

A tracer model nowcast/forecast study of the Tampa Bay, Piney Point effluent plume: Rapid response to an environmental hazard - Yonggang Liu; Robert H. Weisberg; Lianyuan Zheng; Yunfang Sun; Jing Chen; Jason A. Law; Chuanmin Hu; Jennifer P. Cannizzaro; Thomas K. Frazer (Marine Pollution Bulletin, 2024)

Observational energy transfers of a spiral cold filament within an anticyclonic eddy - Chunhua Qiu; Zihao Yang; Ming Feng; Jun Yang; Tom P. Rippeth; Xiaodong Shang; Zhenyu Sun; Chunsheng Jing; Dongxiao Wang (Progress in Oceanography, 2024)

Absorption mechanism and thermodynamics of SO2 using pH-buffered ionic liquid aqueous solution - X. Li; T. Zhang; Y. Liu; Y. Qi; P. Liu; L. Fang; D. Sun (International Journal of Environmental Science and Technology, 2024)

Evolution and exhumation of intrusive rocks associated with the Naozhi porphyry–epithermal system, NE China - Yang Liu; Jinggui Sun; Pete Hollings; Barry P. Kohn; Matthew J. Brzozowski (Contributions to Mineralogy and Petrology, 2024)

Surface subsidence and its reclamation of a coal mine locating at the high groundwater table, China - Z. H. Wang; S. X. Wu; J. L. Li; W. C. Sun; Z. F. Wang; P. J. Liu (International Journal of Environmental Science and Technology, 2023)

Assessing the genetic diversity of Nymphoides peltata in the native and adventive range using microsatellite markers - Nicholas P. Tippery; Nathan E. Harms; Matthew F. Purcell; Sun Hee Hong; Patrick Häfliger; Katelin Killoy; Ashley L. Wolfe; Ryan A. Thum (Biological Invasions, 2023)

A Chewing Study of Abuse-Deterrent Tablets Containing Polyethylene Oxide Using a Robotic Simulator - Bangxiang Chen; Feng Zhang; Jaspreet Dhupia; Marco P. Morgenstern; Mark Costello; Heather Boyce; Wei-Jhe Sun; Saeid Raofi; Li Tian; Weiliang Xu (AAPS PharmSciTech, 2023)

In situ fabrication of Ag decorated porous ZnO photocatalyst via inorganic–organic hybrid transformation for degradation of organic pollutant and bacterial inactivation - Min Seok Song; Ruturaj P. Patil; In Seon Hwang; Mahadeo A. Mahadik; Tae-Hu Jang; Byung Taek Oh; Weon-Sik Chae; Sun Hee Choi; Hyun Hwi Lee; Jum Suk Jang (Chemosphere, 2023)

The importance of pore-fracture connectivity in overmature marine shale for methane occurrence and transportation - Mengdi Sun; Xianggang Duan; Qing Liu; Tomasz P. Blach; Mehdi Ostadhassan; Bo Liu; Yeping Ji; Qinhong Hu; Zhejun Pan (Marine and Petroleum Geology, 2023)

Development of the consider cubature Kalman filter for state estimation of hydrological models with parameter uncertainty - Y. Sun; W. Bao; S. Qu; Q. Li; P. Jiang; Z. Zhou; P. Shi (Journal of Hydrology, 2023)

Theoretically derived pore geometry in carbonates using the extended biot theory - Ralf J. Weger; Gregor P. Eberli; Jose Luis Massaferro; Yuefeng Sun; Gregor T. Baechle (Marine and Petroleum Geology, 2023)

Distribution, abundance, and risks posed by microplastics in surface waters of the Yangtze River Basin, China - Hao Yang; Fuhong Sun; Haiqing Liao; Yiding Guo; Ting Pan; Fengchang Wu; John P. Giesy (Environmental Pollution, 2023)

The potential of biochar as a microbial carrier for agricultural and environmental applications - Shiv Bolan; Deyi Hou; Liuwei Wang; Lauren Hale; Dilfuza Egamberdieva; Priit Tammeorg; Rui Li; Bing Wang; Jiaping Xu; Ting Wang; Hongwen Sun; Lokesh P. Padhye; et al. (Science of The Total Environment, 2023)

Significance of Microglial Energy Metabolism in Maintaining Brain Homeostasis - John P. Bielanin; Dandan Sun (Translational Stroke Research, 2023)

Microglia Signaling Pathway Reporters Unveiled Manganese Activation of the Interferon/STAT1 Pathway and Its Mitigation by Flavonoids - Valeri V. Mossine; James K. Waters; Grace Y. Sun; Zezong Gu; Thomas P. Mawhinney (Molecular Neurobiology, 2023)
Neuroinflammatory responses to neurotoxic manganese (Mn) in CNS have been associated with the Mn-induced Parkinson-like syndromes. However, the framework of molecular mechanisms contributing to manganism is still unclear. Using an in vitro neuroinflammation model based on the insulated signaling pathway reporter transposon constructs stably transfected into a murine BV-2 microglia line, we tested effects of manganese (II) together with a set of 12 metal salts on the transcriptional activities of the NF-κB, activator protein-1 (AP-1), signal transducer and activator of transcription 1 (STAT1), STAT1/STAT2, STAT3, Nrf2, and metal-responsive transcription factor-1 (MTF-1) via luciferase assay, while concatenated destabilized green fluorescent protein expression provided for simultaneous evaluation of cellular viability. This experiment revealed specific and strong responses to manganese (II) in reporters of the type I and type II interferon-induced signaling pathways, while weaker activation of the NF-κB in the microglia was detected upon treatment of cells with Mn(II) and Ba(II). There was a similarity between Mn(II) and interferon-γ in the temporal STAT1 activation profile and in their antagonism to bacterial LPS. Sixty-four natural and synthetic flavonoids differentially affected both cytotoxicity and the pro-inflammatory activity of Mn (II) in the microglia. Whereas flavan-3-ols, flavanones, flavones, and flavonols were cytoprotective, isoflavones enhanced the cytotoxicity of Mn(II). Furthermore, about half of the tested flavonoids at 10–50 μM could attenuate both basal and 100–200 μM Mn(II)-induced activity at the gamma-interferon activated DNA sequence (GAS) in the cells, suggesting no critical roles for the metal chelation or antioxidant activity in the protective potential of flavonoids against manganese in microglia. In summary, results of the study identified Mn as a specific elicitor of the interferon-dependent pathways that can be mitigated by dietary polyphenols.

An improved method for determining frequency of multiple variants of SARS-CoV-2 in wastewater using qPCR assays - Meghan Fuzzen; Nathanael B.J. Harper; Hadi A. Dhiyebi; Nivetha Srikanthan; Samina Hayat; Leslie M. Bragg; Shelley W. Peterson; Ivy Yang; J.X. Sun; Elizabeth A. Edwards; John P. Giesy; Chand S. Mangat; et al. (Science of The Total Environment, 2023)

Status, challenges and pathways to the sustainable use of wild species - Jean-Marc Fromentin; Marla R. Emery; John Donaldson; Ganesan Balachander; Elizabeth S. Barron; Ram P. Chaudhary; Marie-Claire Danner; Maria A. Gasalla; Agnès Hallosserie; Marwa Halmy; Christina Hicks; Daniel Kieling; et al. (Global Environmental Change, 2023)

Zoning strategies for managing outbreaks of alien plant pests in the European Union: a review - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Roel P. J. Potting; Donato Boscia; Antonio Vicent; Alan MacLeod; Wopke van der Werf (Journal of Pest Science, 2023)
Managing outbreaks of alien plant pests is key to preserving biodiversity and safeguarding crop production. Zoning strategies are applied by plant health authorities to tailor measures to the risk of spread in relation to distance from the outbreak epicentre and the biology of the pest. Here we synthesize information on outbreak management to evaluate the diversity and consistency of such approaches. We collected information on the zoning strategies of 121 outbreaks of 25 plant pests in the European Union (EU). According to the organism’s presence and the measures applied, five zones were distinguished: an infested zone (83% of cases), a buffer zone (76%), a clear-cutting zone (28%), an eradication zone (1%) and a containment zone (1%). Infested zones and buffer zones were adjacent non-overlapping zones, while the clear-cutting zone, eradication zone or containment zone was within either the infested zone or buffer zone. A combination of infested and buffer zones was used in 51% of recorded cases. Measures differed within different zones. Destruction of infested plants in the infested zone was done in 78% of the cases, while surveillance was always applied in the buffer zone. Regulation of an organism at EU level led to a convergence of zoning strategies applied by different member states. Regulations often prescribed the greatest widths used before regulations were issued. Further analyses are needed to explore the efficacy of different strategies including the costs of each strategy. Such analyses should combine insight from practice with bio-economic modelling.

Adverse health effects and stresses on offspring due to paternal exposure to harmful substances - Jiaqi Sun; Miaomiao Teng; Fengchang Wu; Xiaoli Zhao; Yunxia Li; Lihui Zhao; Wentian Zhao; Keng Po Lai; Kenneth Mei Yee Leung; John P. Giesy (Critical Reviews in Environmental Science and Technology, 2023)

Climate and edaphic factors drive soil nematode diversity and community composition in urban ecosystems - Xin Gong; Xin Sun; Madhav P. Thakur; Zhihong Qiao; Haifeng Yao; Manqiang Liu; Stefan Scheu; Yong-Guan Zhu (Soil Biology and Biochemistry, 2023)

RETRACTED: Toxicity of perfluorobutanesulfonate on gill functions of marine medaka (Oryzias melastigma): A time course and hypoxia co-exposure study - Baili Sun; Jing Li; Chenyan Hu; John P. Giesy; Paul K.S. Lam; Lianguo Chen (Science of The Total Environment, 2023)

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Current and future potential soil organic carbon stocks of vegetated coastal ecosystems and their controls in the Bohai Rim Region, China - Shaobo Sun; Zhaoliang Song; Baozhang Chen; Yidong Wang; Xiangbin Ran; Yunying Fang; Lukas Van Zwieten; Iain P. Hartley; Yafei Wang; Qiang Li; Lele Wu; Cong-Qiang Liu; et al. (CATENA, 2023)

Microplastics in different water samples (seawater, freshwater, and wastewater): Methodology approach for characterization using micro-FTIR spectroscopy - J. Yang; M. Monnot; Y. Sun; L. Asia; P. Wong-Wah-Chung; P. Doumenq; P. Moulin (Water Research, 2023)

Microplastics in different water samples (seawater, freshwater, and wastewater): Removal efficiency of membrane treatment processes - J. Yang; M. Monnot; Y. Sun; L. Asia; P. Wong-Wah-Chung; P. Doumenq; P. Moulin (Water Research, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

The potential meat flavoring generated from Maillard reaction products of wheat gluten protein hydrolysates-xylose: Impacts of different thermal treatment temperatures on flavor - Ao Sun; Lining Chen; Wei Wu; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Food Research International, 2023)

Evolution of diagenetic fluids in the deeply buried, upper Ediacaran Dengying Formation, Central Sichuan Basin, China - Y. J. Hu; C. F. Cai; Y. Li; R. Zhou; Y. J. Tang; J. F. Hu; F. C. Lu; P. Sun (Australian Journal of Earth Sciences, 2023)

Uniformity and volume-representativity of consecutive submillimetre wafers of shale for SANS and USANS investigations - Yeping Ji; Andrzej P. Radlinski; Tomasz Blach; Phung Vu; Mengdi Sun; Liliana de Campo; Elliot P. Gilbert; Hamid Roshan; Klaus Regenauer-Lieb (International Journal of Coal Geology, 2023)

2, 3, 4, 5, 6-Pentafluorophenylammonium bromide-based double-sided interface engineering for efficient planar heterojunction perovskite solar cells - Beibei Zong; Die Hu; Qing Sun; Jianguo Deng; Zizhao Zhang; Xiangxin Meng; Bo Shen; Bonan Kang; S. Ravi P. Silva; Geyu Lu (Chemical Engineering Journal, 2023)

Diversity in financing and implementation pathways for industrial symbiosis across the globe - Zhe Liu; Weslynne S. Ashton; Michelle Adams; Qing Wang; Raymond P. Cote; Tony R. Walker; Lu Sun; Peter Lowitt (Environment, Development and Sustainability, 2023)

In vitro degradation and erosion behavior of commercial PLGAs used for controlled drug delivery - Jennifer Walker; Jason Albert; Desheng Liang; Jing Sun; Richard Schutzman; Raj Kumar; Cameron White; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2023)

Aqueous N -nitrosamines: Precursors, occurrence, oxidation processes, and role of inorganic ions - Tahereh Jasemizad; Peizhe Sun; Lokesh P. Padhye (Critical Reviews in Environmental Science and Technology, 2022)

Indirect effects of cleaner fish Labroides dimidiatus on fish grazing per reef area and benthic community structure - A. S. Grutter; S. Bejarano; D. Sun; P. J. Mumby (Marine Biology, 2022)
Grazing fishes farm algae, and consume algae, detritus and sediment and consequently differentially modify benthic communities. Manipulations of cleaner fish Labroides dimidiatus on reefs show that cleaners affect fish abundance differently according to grazer functional group. Accordingly, whether reefs are grazed differently, with consequences for the benthos (fouling material tile −1 ), was tested using reefs kept free of L. dimidiatus for 10 years compared with undisturbed control reefs. We recorded on video the grazing density (bites tile −1 h −1 reef −1 ) on settlement tiles and the natural benthos (roving fishes only), according to territorial algal farmer (Pomacentridae) and roving grazer (Acanthuridae, Labridae, Siganidae) functional groups, and measured the accumulation of fouling material tile −1 after 10 months. Grazing density on tiles (dominated by ‘indeterminate’ farmers, and roving ‘sediment-removing’ detritivore Ctenochaetus striatus ) and the natural benthos (dominated by Ct. striatus and other grazers) was not measurably affected by cleaner presence. The composition of fouling material (dominated by detritus > turf algae > sediment > other) and organic and inorganic dry weight of material tile −1 were also not measurably affected by cleaner presence. This points to resilience of the benthic community to loss of cleaners. The likely complex interactions between cleaner fish presence, grazer abundance and mobility, and the often-opposite effects of territorial farmers and roving grazers on the benthos underscore the challenge in determining indirect effects of cleaners on benthic community structure. However, a lack of cleaners has negative ramifications for fish populations and physiology and thus their loss remains problematic for client fishes.

Seasonal non-structural carbohydrate dynamics differ between twig bark and xylem tissues - Liyuan Gao; Doug P. Aubrey; Xingchang Wang; Huizhen Sun (Trees, 2022)

Improving generation of H2O2 and ·OH at bismuth hexacyanoferrate/graphene/carbon fibers-based gas diffusion electrode for degradation of dye wastewaters in photo-electro-Fenton process - T. Chen; G. -P. Jin; Z. Xu; X. -Y. Lv; M. Sun; J. -J. Tian (International Journal of Environmental Science and Technology, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Absence of hydrothermal oxygen isotope variations in host rocks supports magmatic origin of the giant Grängesberg iron oxide–apatite (IOA) deposit, Central Sweden - Franz Weis; Valentin R. Troll; Erik Jonsson; Karin Högdahl; Chris Harris; Weian Sun; Katarina P. Nilsson; Börje Dahrén (International Journal of Earth Sciences, 2022)
The origin of Kiruna-type iron oxide–apatite ores is controversial, and debate presently centres on a ‘magmatic’ versus a ‘hydrothermal’ mode of formation. To complement recent investigations on the Grängesberg iron oxide–apatite ore deposit in the northwestern part of the Palaeoproterozoic Bergslagen ore province in central Sweden, we investigated the oxygen isotope composition of the host rocks of this large iron oxide–apatite ore body. As the metavolcanic and metagranitoid country rocks around the Grängesberg ore body either pre-date or are coeval with ore formation, they would be expected to record an extensive isotopic imprint if the ore body had formed by large-scale hydrothermal processes involving an externally sourced fluid. A direct magmatic formation process, in turn, would have produced localized alteration only, concentrated on the immediate vicinity of the ore body. Here, we test these two hypotheses by assessing the oxygen isotope variations in the host rocks around the main Grängesberg iron oxide–apatite ore body. We analysed oxygen isotopes in quartz from metavolcanic ( n = 17) and metagranitoid host rocks ( n = 14) from the vicinity of the ore body, and up to 2 km distance along and across the strike of the ore body. Remarkably, we find no significant variation in δ 18 O values with distance from the ore body, or any deviations in country rock δ 18 O from common magmatic and/or regional values. Only two samples show shifts to values more negative than the common magmatic range, indicating highly localized hydrothermal overprint only. As a large-scale, low-temperature hydrothermal origin of the ore body through voluminous fluid percolation would be expected to have left a distinct imprint on the oxygen isotope values of the country rocks, our results are more consistent with an ortho-magmatic origin for the Grängesberg iron oxide–apatite ore.

Correction to: Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck‑Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

The Status of Iodine Nutrition after Removing Iodized Salt in High Water Iodine Regions: a Cross-sectional Study in China - J. Yao; W. Zhang; J. Wang; K. Wang; C. Lv; Z. Zhang; X. Chen; Y. Chen; W. Jiang; J. Niu; F. Song; P. Liu; et al. (Biological Trace Element Research, 2022)

Oxidation of organoarsenicals and antimonite by a novel flavin monooxygenase widely present in soil bacteria - Jun Zhang; Jian Chen; Yi‐Fei Wu; Zi‐Ping Wang; Ji‐Guo Qiu; Xiao‐Long Li; Feng Cai; Ke‐Qing Xiao; Xiao‐Xu Sun; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Arsenic can be biomethylated to form a variety of organic arsenicals differing in toxicity and environmental mobility. Trivalent methylarsenite (MAs(III)) produced in the methylation process is more toxic than inorganic arsenite (As(III)). MAs(III) also serves as a primitive antibiotic and, consequently, some environmental microorganisms have evolved mechanisms to detoxify MAs(III). However, the mechanisms of MAs(III) detoxification are not well understood. In this study, we identified an arsenic resistance ( ars ) operon consisting of three genes, arsRVK , that contribute to MAs(III) resistance in Ensifer adhaerens ST2. ArsV is annotated as an NADPH‐dependent flavin monooxygenase with unknown function. Expression of arsV in the arsenic hypersensitive Escherichia coli strain AW3110 Δars conferred resistance to MAs(III) and the ability to oxidize MAs(III) to MAs(V). In the presence of NADPH and either FAD or FMN, purified ArsV protein was able to oxidize both MAs(III) to MAs(V) and Sb(III) to Sb(V). Genes with arsV ‐like sequences are widely present in soils and environmental bacteria. Metagenomic analysis of five paddy soils showed the abundance of arsV ‐like sequences of 0.12–0.25 ppm. These results demonstrate that ArsV is a novel enzyme for the detoxification of MAs(III) and Sb(III) and the genes encoding ArsV are widely present in soil bacteria.

A critical review on soil washing during soil remediation for heavy metals and organic pollutants - J. Liu; L. Zhao; Q. Liu; J. Li; Z. Qiao; P. Sun; Y. Yang (International Journal of Environmental Science and Technology, 2022)

Station‐based non‐linear regression downscaling approach: A new monthly precipitation downscaling technique - Zexi Shen; Qiang Zhang; Vijay P. Singh; Peng Sun; Chunyang He; Changxiu Cheng (International Journal of Climatology, 2021)
Statistical downscaling is an effective way to downscale General Circulation Model (GCM) outputs to a finer temporal and spatial scale. Here, we proposed and trained a new station‐based non‐linear regression downscaling (SNRD) approach, and quantitatively demonstrated its better performance than linear regression model. In addition, we also compared the SNRD method with the Bias Correction Spatial Disaggregation (BCSD) method, which has been widely applied on downscaling precipitation. Results indicated that RMSEs and residuals of the BCSD method are 4.6–31 times as ones of SNRD in each region of China during validation period (2004–2015). Besides, with historical in‐situ observed monthly mean precipitation as the benchmark, SNRD downscaled model modified the over‐estimation (1.25–2 times as observed precipitation) flaw of BCSD model in rainy season (June–August) of China, which could provide assistance on the further researches on drought events in rainy season in future. Further, we also surprisingly found that the 2,500 m was the threshold height for statistical downscaling models. Both BCSD and SNRD downscaled precipitation displayed more steadily and accurately above 2,500 m, since there are less intense human activities in China. Thus, we recommend further studies should fully consider the height element in downscaling models to improve the accuracies.

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

The model tests of rainfall infiltration in two-layer unsaturated soil slopes - L. Z. Wu; R. Q. Huang; H. L. Li; X. Li; P. Sun (European Journal of Environmental and Civil Engineering, 2021)

Improved genomic prediction of clonal performance in sugarcane by exploiting non-additive genetic effects - Seema Yadav; Xianming Wei; Priya Joyce; Felicity Atkin; Emily Deomano; Yue Sun; Loan T. Nguyen; Elizabeth M. Ross; Tony Cavallaro; Karen S. Aitken; Ben J. Hayes; Kai P. Voss-Fels (Theoretical and Applied Genetics, 2021)
Key message Non-additive genetic effects seem to play a substantial role in the expression of complex traits in sugarcane. Including non-additive effects in genomic prediction models significantly improves the prediction accuracy of clonal performance. Abstract In the recent decade, genetic progress has been slow in sugarcane. One reason might be that non-additive genetic effects contribute substantially to complex traits. Dense marker information provides the opportunity to exploit non-additive effects in genomic prediction. In this study, a series of genomic best linear unbiased prediction (GBLUP) models that account for additive and non-additive effects were assessed to improve the accuracy of clonal prediction. The reproducible kernel Hilbert space model, which captures non-additive genetic effects, was also tested. The models were compared using 3,006 genotyped elite clones measured for cane per hectare (TCH), commercial cane sugar (CCS), and Fibre content. Three forward prediction scenarios were considered to investigate the robustness of genomic prediction. By using a pseudo-diploid parameterization, we found significant non-additive effects that accounted for almost two-thirds of the total genetic variance for TCH. Average heterozygosity also had a major impact on TCH, indicating that directional dominance may be an important source of phenotypic variation for this trait. The extended-GBLUP model improved the prediction accuracies by at least 17% for TCH, but no improvement was observed for CCS and Fibre. Our results imply that non-additive genetic variance is important for complex traits in sugarcane, although further work is required to better understand the variance component partitioning in a highly polyploid context. Genomics-based breeding will likely benefit from exploiting non-additive genetic effects, especially in designing crossing schemes. These findings can help to improve clonal prediction, enabling a more accurate identification of variety candidates for the sugarcane industry.

Fine-Scale Air Pollution Models for Epidemiologic Research: Insights From Approaches Developed in the Multi-ethnic Study of Atherosclerosis and Air Pollution (MESA Air) - Kipruto Kirwa; Adam A. Szpiro; Lianne Sheppard; Paul D. Sampson; Meng Wang; Joshua P. Keller; Michael T. Young; Sun-Young Kim; Timothy V. Larson; Joel D. Kaufman (Current Environmental Health Reports, 2021)

Characterization of Anisotropic Fracture Properties of Silurian Longmaxi Shale - L. Ren; H. P. Xie; X. Sun; R. Zhang; C. B. Li; J. Xie; Z. T. Zhang (Rock Mechanics and Rock Engineering, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

A Comprehensive Experimental Study on Mechanical Behavior, Microstructure and Transport Properties of 3D-printed Rock Analogs - Rui Song; Yao Wang; Sergey Ishutov; Gonzalo Zambrano-Narvaez; Kevin J. Hodder; Rick J. Chalaturnyk; Shuyu Sun; Jianjun Liu; Ranjith P. Gamage (Rock Mechanics and Rock Engineering, 2020)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Using genomic tools to inform management of the Atlantic northern fulmar - Lila Colston-Nepali; Jennifer F. Provencher; Mark L. Mallory; Ryan P. Franckowiak; Zhengxin Sun; Gregory J. Robertson; Vicki L. Friesen (Conservation Genetics, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Azaphilones biosynthesis complements the defence mechanism of Trichoderma guizhouense against oxidative stress - Guan Pang; Tingting Sun; Zhenzhong Yu; Tao Yuan; Wei Liu; Hong Zhu; Qi Gao; Dongqing Yang; Christian P. Kubicek; Jian Zhang; Qirong Shen (Environmental Microbiology, 2020)
Summary Filamentous fungi are known as producers of a large array of diverse secondary metabolites (SMs) that aid in securing their environmental niche. Here, we demonstrated that the SMs have an additional role in fungal defence against other fungi: Trichoderma guizhouense , a mycoparasite, is able to antagonize Fusarium oxysporum f. sp. cubense race 4 (Foc4) by forming aerial hyphae that kill the host with hydrogen peroxide. At the same time, a gene cluster comprising two polyketide synthases is strongly expressed. Using functional genetics, we characterized this cluster and identified its products as azaphilones (termed as trigazaphilones). The trigazaphilones were found lacking of antifungal toxicity but exhibited high radical scavenging activities. The antioxidant property of trigazaphilones was in vivo functional under various tested conditions of oxidative stress. Thus, we conclude that the biosynthesis of trigazaphilones serves as a complementary antioxidant mechanism and defends T. guizhouense against the hydrogen peroxide that it produces to combat other fungi like Foc4.

A two-stage fuzzy-stochastic factorial analysis method for characterizing effects of uncertainties in hydrological modelling - Y. R. Liu; Y. P. Li; J. Sun (Hydrological Sciences Journal, 2020)

Effect of pavement and water deficit on biomass allocation and whole-tree transpiration in two contrasting urban tree species - Xuming Wang; Xiaoke Wang; Xu Sun; Graeme P. Berlyn; Abdur Rehim (Urban Ecosystems, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Therapeutic effect of methane and its mechanism in disease treatment - Zhou-heng Ye; Ke Ning; Bradley P. Ander; Xue-jun Sun (Journal of Zhejiang University-SCIENCE B, 2020)

Understanding Environmental Changes in Temperate Coastal Seas: Linking Models of Benthic Fauna to Carbon and Nutrient Fluxes - Eva Ehrnsten; Xiaole Sun; Christoph Humborg; Alf Norkko; Oleg P. Savchuk; Caroline P. Slomp; Karen Timmermann; Bo G. Gustafsson (Frontiers in Marine Science, 2020)

Thermal and mechanical evolution of collisional and accretionary orogens: a volume in honour of Karel Schulmann—an introduction - P. Štípská; P. Hasalová; P. Jeřábek; O. Lexa; J. M. Lardeaux; M. Sun; J. W. Cosgrove (International Journal of Earth Sciences, 2020)

Parameter Analysis and Field Tests of a Double Crank Multi-Rod under Plastic-Film Hill-Drop Mechanism Potato Planter - Wei Sun; P. A. Simionescu (American Journal of Potato Research, 2020)

Changing coupling between the arms and legs with slow walking speeds alters regulation of somatosensory feedback - Taryn Klarner; Gregory E. P. Pearcey; Yao Sun; Trevor S. Barss; E. Paul Zehr (Experimental Brain Research, 2020)

Provenance analysis of the Cretaceous Laiyang Group on Lingshan Island (western Yellow Sea, China) and its tectono-sedimentary implications - A. P. Fan; S. N. Sun; R. C. Yang; Z. Zhang; S. De; J. D. N. Nenzhelele; Y. Li; H. P. Liu; Y. Q. Zhou; J. Yuan (Australian Journal of Earth Sciences, 2020)

mGlu5 in GABAergic neurons modulates spontaneous and psychostimulant-induced locomotor activity - Chia-Shan Wu; Christopher P. Jew; Hao Sun; Carlos J. Ballester Rosado; Hui-Chen Lu (Psychopharmacology, 2020)

Enhanced somatosensory feedback modulates cutaneous reflexes in arm muscles during self-triggered or prolonged stimulation - Yao Sun; Gregory E. P. Pearcey; E. Paul Zehr (Experimental Brain Research, 2020)

Mechanistic Deconvolution of Oral Absorption Model with Dynamic Gastrointestinal Fluid to Predict Regional Rate and Extent of GI Drug Dissolution - Alex Yu; Mark J. Koenigsknecht; Bart Hens; Jason R. Baker; Bo Wen; Trachette L. Jackson; Manjunath P. Pai; William Hasler; Gordon L. Amidon; Duxin Sun (The AAPS Journal, 2020)

Predicting blast-induced outcomes using random forest models of multi-year blasting data from an open pit mine - Behrouz Ohadi; Xi Sun; Kamran Esmaieli; Mariano P. Consens (Bulletin of Engineering Geology and the Environment, 2020)

Evaluation of potential genetic and chemical markers for Scots pine tolerance against Heterobasidion annosum infection - Mukrimin Mukrimin; Andriy Kovalchuk; Rajendra P. Ghimire; Minna Kivimäenpää; Hui Sun; Jarmo K. Holopainen; Fred O. Asiegbu (Planta, 2019)

A Review on Marine N2 Fixation: Mechanism, Evolution of Methodologies, Rates, and Future Concerns - P. S. Bhavya; Jun-Oh Min; Min-Seob Kim; Hyo Keun Jang; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Naeun Jo; Myung Joon Kim; Yejin Kim; Junbeom Lee; et al. (Ocean Science Journal, 2019)

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

Shear Creep Tests on Fissured Mudstone and an Improved Time-Dependent Model - L. Z. Wu; S. H. Li; P. Sun; R. Q. Huang; B. Li (Pure and Applied Geophysics, 2019)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Correction to: Atmospheric Stability Effects on Wind Fields and Scalar Mixing Within and Just Above a Subalpine Forest in Sloping Terrain - Sean P. Burns; Jielun Sun; Donald H. Lenschow; Steven P. Oncley; Britton B. Stephens; Chuixiang Yi; Dean E. Anderson; Jia Hu; Russell K. Monson (Boundary-Layer Meteorology, 2019)

For common community phylogenetic analyses, go ahead and use synthesis phylogenies - Daijiang Li; Lauren Trotta; Hannah E. Marx; Julie M. Allen; Miao Sun; Douglas E. Soltis; Pamela S. Soltis; Robert P. Guralnick; Benjamin Baiser (Ecology, 2019)
Should we build our own phylogenetic trees based on gene sequence data, or can we simply use available synthesis phylogenies? This is a fundamental question that any study involving a phylogenetic framework must face at the beginning of the project. Building a phylogeny from gene sequence data (purpose‐built phylogeny) requires more effort, expertise, and cost than subsetting an already available phylogeny (synthesis‐based phylogeny). However, we still lack a comparison of how these two approaches to building phylogenetic trees influence common community phylogenetic analyses such as comparing community phylogenetic diversity and estimating trait phylogenetic signal. Here, we generated three purpose‐built phylogenies and their corresponding synthesis‐based trees (two from Phylomatic and one from the Open Tree of Life, OTL ). We simulated 1,000 communities and 12,000 continuous traits along each purpose‐built phylogeny. We then compared the effects of different trees on estimates of phylogenetic diversity (alpha and beta) and phylogenetic signal (Pagel's λ and Blomberg's K). Synthesis‐based phylogenies generally yielded higher estimates of phylogenetic diversity when compared to purpose‐built phylogenies. However, resulting measures of phylogenetic diversity from both types of phylogenies were highly correlated (Spearman's > 0.8 in most cases). Mean pairwise distance (both alpha and beta) is the index that is most robust to the differences in tree construction that we tested. Measures of phylogenetic diversity based on the OTL showed the highest correlation with measures based on the purpose‐built phylogenies. Trait phylogenetic signal estimated with synthesis‐based phylogenies, especially from the OTL , was also highly correlated with estimates of Blomberg's K or close to Pagel's λ from purpose‐built phylogenies when traits were simulated under Brownian motion. For commonly employed community phylogenetic analyses, our results justify taking advantage of recently developed and continuously improving synthesis trees, especially the Open Tree of Life.

Identifying changes and critical drivers of future temperature and precipitation with a hybrid stepwise-cluster variance analysis method - J. Sun; Y. P. Li; C. Suo; G. H. Huang (Theoretical and Applied Climatology, 2019)

Changes in local free-living parasite populations in response to cleaner manipulation over 12 years - A. S. Grutter; S. P. Blomberg; S. Box; R. Bshary; O. Ho; E. M. P. Madin; E. C. McClure; M. G. Meekan; J. M. Murphy; M. A. Richardson; P. C. Sikkel; C. A. Sims; et al. (Oecologia, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

Changes in abundance of fish-parasitic gnathiid isopods associated with warm-water bleaching events on the northern Great Barrier Reef - P. C. Sikkel; M. A. Richardson; D. Sun; P. Narvaez; W. E. Feeney; A. S. Grutter (Coral Reefs, 2019)

High-throughput phenotyping platforms enhance genomic selection for wheat grain yield across populations and cycles in early stage - Jin Sun; Jesse A. Poland; Suchismita Mondal; José Crossa; Philomin Juliana; Ravi P. Singh; Jessica E. Rutkoski; Jean-Luc Jannink; Leonardo Crespo-Herrera; Govindan Velu; Julio Huerta-Espino; Mark E. Sorrells (Theoretical and Applied Genetics, 2019)

Skeletal muscle proteome analysis provides insights on high altitude adaptation of yaks - Wenting Wen; Zheze Zhao; Ruolin Li; Jiuqiang Guan; Zhiwei Zhou; Xiaolin Luo; Surendranath P. Suman; Qun Sun (Molecular Biology Reports, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Social connectivity among female Tibetan macaques (Macaca thibetana) increases the speed of collective movements - Gregory P. Fratellone; Jin-Hua Li; Lori K. Sheeran; R. S. Wagner; Xi Wang; Lixing Sun (Primates, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

Potential contributions of climate change and urbanization to precipitation trends across China at national, regional and local scales - Xihui Gu; Qiang Zhang; Vijay P. Singh; Changqing Song; Peng Sun; Jianfeng Li (International Journal of Climatology, 2019)
Climate change and urbanization collectively influence precipitation changes. However, their separate potential contributions to precipitation changes are not well understood due to their complex interactions. Hence, a “trajectory”‐based method was used to separate their potential contributions across national, regional and local scales in China. Precipitation changes in non‐urban regions can be regarded as representing the influence of climate change and can serve as a reference for isolating precipitation changes due to urbanization in urban areas. Our results revealed that climate change was the dominant factor for precipitation trends, while urbanization exhibited a relatively weak influence, especially for extreme precipitation at the national scale. At the regional scale, the impacts of urbanization on precipitation became more significant. About 20.2 and −30.6% of positive and negative trends in total precipitation originated from urbanization. At the local scale, the potential contribution of urbanization was strongly correlated with local environmental characteristics. Although there were differences in the potential contributions of climate change and urbanization at national, regional and local scales, climate change was the dominant factor for precipitation trends and urbanization acted as a regulator to drying or wetting due to precipitation under climate change. In general, urbanization causes a greater impact on total precipitation than on precipitation extremes. Due to this, attribution approach is static and broad‐based and does not render the level of confidence that is needed for scale‐aware attribution, future studies are needed to understand the physical mechanisms of impacts of local environment changes on precipitation trends at different geographical locations over China.

Versican silencing in BeWo cells and its implication in gestational trophoblastic diseases - Keyla S. N. Pires; Sue Y. Sun; Camilla M. Gonçalves; Jaqueline C. Santos; Liliane P. G. Tenorio; Rayane M. Botelho; Ana Lucia M. Silva; Hillary Gabriela S. Oliveira; Karen Priscila T. Pendeloski; Silvia Daher; Karen S. C. Borbely; Alexandre U. Borbely (Histochemistry and Cell Biology, 2019)

Parasites of coral reef fish larvae: its role in the pelagic larval stage - B. Duong; S. P. Blomberg; T. H. Cribb; P. F. Cowman; A. M. Kuris; M. I. McCormick; R. R. Warner; D. Sun; A. S. Grutter (Coral Reefs, 2019)

Diagnostics of plasma reactive species and induced chemistry of plasma treated foods - Kexin Zhang; Camila A. Perussello; Vladimir Milosavljević; P. J. Cullen; Da-Wen Sun; Brijesh K. Tiwari (Critical Reviews in Food Science and Nutrition, 2019)

An evolutionarily conserved non-synonymous SNP in a leucine-rich repeat domain determines anthracnose resistance in watermelon - Yoon Jeong Jang; Minseok Seo; Craig P. Hersh; Sun-Ju Rhee; Yongjae Kim; Gung Pyo Lee (Theoretical and Applied Genetics, 2019)

Effects of planting patterns on the concentration and bioavailability of heavy metals in soils during wetland restoration - H. Su; P. Guo; Y. Zhang; J. Deng; M. Wang; Y. Sun; Y. Wu (International Journal of Environmental Science and Technology, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Diagenesis impact on a deeply buried sandstone reservoir (Es 1 Member) of the Shahejie Formation, Nanpu Sag, Bohai Bay Basin, East China - M. Kashif; Y. Cao; G. Yuan; W. Jian; X. Cheng; P. Sun; S. Hassan (Australian Journal of Earth Sciences, 2019)

A Review on the Macromolecular Compositions of Phytoplankton and the Implications for Aquatic Biogeochemistry - P. S. Bhavya; Bo Kyung Kim; Naeun Jo; Kwanwoo Kim; Jae Joong Kang; Jae Hyung Lee; Dabin Lee; Jang Han Lee; HuiTae Joo; So Hyun Ahn; Yewon Kim; Jun-Oh Min; et al. (Ocean Science Journal, 2019)

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Apolipoprotein E Exerts a Whole-Brain Protective Property by Promoting M1? Microglia Quiescence After Experimental Subarachnoid Hemorrhage in Mice - Jinwei Pang; Jianhua Peng; Nathanael Matei; Ping Yang; Li Kuai; Yue Wu; Ligang Chen; Michael P. Vitek; Fengqiao Li; Xiaochuan Sun; John H. Zhang; Yong Jiang (Translational Stroke Research, 2018)

Increased Soil Frost Versus Summer Drought as Drivers of Plant Biomass Responses to Reduced Precipitation: Results from a Globally Coordinated Field Experiment - Hugh A. L. Henry; Mehdi Abedi; Concepción L. Alados; Karen H. Beard; Lauchlan H. Fraser; Anke Jentsch; Juergen Kreyling; Andrew Kulmatiski; Eric G. Lamb; Wei Sun; Mathew R. Vankoughnett; Susanna Venn; et al. (Ecosystems, 2018)

Distribution of inositol phosphates in animal feed grains and excreta: distinctions among isomers and phosphate oxygen isotope compositions - Mingjing Sun; Deb P. Jaisi (Plant and Soil, 2018)

Development of social sustainability assessment method and a comparative case study on assessing recycled construction materials - Md. Uzzal Hossain; Chi Sun Poon; Ya Hong Dong; Irene M. C. Lo; Jack C. P. Cheng (The International Journal of Life Cycle Assessment, 2018)

Groundwater sustainability and groundwater/surface-water interaction in arid Dunhuang Basin, northwest China - Jingjing Lin; Rui Ma; Yalu Hu; Ziyong Sun; Yanxin Wang; Colin P. R. McCarter (Hydrogeology Journal, 2018)

Rapid visual detection of cyprinid herpesvirus 2 by recombinase polymerase amplification combined with a lateral flow dipstick - H Wang; M Sun; D Xu; P Podok; J Xie; Ys Jiang; Lq Lu (Journal of Fish Diseases, 2018)
Herpesviral haematopoietic necrosis ( HVHN ), caused by cyprinid herpesvirus 2 (Cy HV ‐2), causes significant losses in crucian carp ( Carassius carassius ) aquaculture. Rapid and convenient DNA assay detection of Cy HV ‐2 is useful for field diagnosis. Recombinase polymerase amplification ( RPA ) is a novel isothermal DNA amplification and detection technology that can amplify DNA within 30 min at ~37°C by simulating in vivo DNA recombination. Herein, a rapid and convenient detection assay based on RPA with a lateral flow dipstick ( LFD ) was developed for detecting Cy HV ‐2. The highly conserved ORF 72 of Cy HV ‐2 was targeted by specific and sensitive primers and probes. The optimized assay takes only 15 min at 38°C using a water bath, with analysis of products by 2% agarose gel electrophoresis within 30 min. A simple lateral flow strip based on the unique probe in reaction buffer was developed for visualization. The entire RPA ‐ LFD assay takes 50 min less than the routine PCR method, is 100 times more sensitive and displays no cross‐reaction with other aquatic viruses. The combined isothermal RPA and lateral flow assay ( RPA ‐ LFD ) provides a simple, rapid, reliable method that could improve field diagnosis of Cy HV ‐2 when resources are limited.

Transcending data gaps: a framework to reduce inferential errors in ecological analyses - Sun W. Kim; Simon P. Blomberg; John M. Pandolfi (Ecology Letters, 2018)
The analysis of functional diversity (FD) has gained increasing importance due to its generality and utility in ecology. In particular, patterns in the spatial distribution and temporal change of FD are being used to predict locations and functional groups that are immediately vulnerable to global changes. A major impediment to the accurate measurement of FD is the pervasiveness of missing data in trait datasets. While such prevalent data gaps can engender misleading inferences in FD analyses, we currently lack any practical guide to handle missing data in trait datasets. Here, we identify significant mismatches between true FD and values derived from datasets that contain missing data. We demonstrate that imputing missing data with a phylogeny‐informed approach reduces the risk of misinterpretation of FD patterns, and provides baseline information against which central questions in ecology can be evaluated.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The role of citrate, lactate and transferrin in determining titanium release from surgical devices into human serum - Justin P. Curtin; Minji Wang; Tianfan Cheng; Lijian Jin; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2018)

Identifying water resources management strategies in adaptation to climate change under uncertainty - J. Sun; Y. P. Li; X. W. Zhuang; S.W. Jin; G. H. Huang; R. F. Feng (Mitigation and Adaptation Strategies for Global Change, 2018)

Ecohydrological effects of water reservoirs with consideration of asynchronous and synchronous concurrences of high- and low-flow regimes - Zhenghao Zhang; Qiang Zhang; Vijay P. Singh; Sun Peng (Hydrological Sciences Journal, 2018)

Validation of α-Synuclein as a CSF Biomarker for Sporadic Creutzfeldt-Jakob Disease - Franc Llorens; Niels Kruse; André Karch; Matthias Schmitz; Saima Zafar; Nadine Gotzmann; Ting Sun; Silja Köchy; Tobias Knipper; Maria Cramm; Ewa Golanska; Beata Sikorska; et al. (Molecular Neurobiology, 2018)

Parasite infestation increases on coral reefs without cleaner fish - A. S. Grutter; M. De Brauwer; R. Bshary; K. L. Cheney; T. H. Cribb; E. M. P. Madin; E. C. McClure; M. G. Meekan; D. Sun; R. R. Warner; J. Werminghausen; P. C. Sikkel (Coral Reefs, 2018)

Localized high abundance of Marine Group II archaea in the subtropical Pearl River Estuary: implications for their niche adaptation - Wei Xie; Haiwei Luo; Senthil K. Murugapiran; Jeremy A. Dodsworth; Songze Chen; Ying Sun; Brian P. Hedlund; Peng Wang; Huaying Fang; Minghua Deng; Chuanlun L. Zhang (Environmental Microbiology, 2018)
Summary Marine Group II archaea are widely distributed in global oceans and dominate the total archaeal community within the upper euphotic zone of temperate waters. However, factors controlling the distribution of MGII are poorly delineated and the physiology and ecological functions of these still‐uncultured organisms remain elusive. In this study, we investigated the planktonic MGII associated with particles and in free‐living forms in the Pearl River Estuary (PRE) over a 10‐month period. We detected high abundance of particle‐associated MGII in PRE (up to ∼10 8 16S rRNA gene copies/l), which was around 10‐fold higher than the free‐living MGII in the same region, and an order of magnitude higher than previously reported in other marine environments. 10‰ salinity appeared to be a threshold value for these MGII because MGII abundance decreased sharply below it. Above 10‰ salinity, the abundance of MGII on the particles was positively correlated with phototrophs and MGII in the surface water was negatively correlated with irradiance. However, the abundances of those free‐living MGII showed positive correlations with salinity and temperature, suggesting the different physiological characteristics between particle‐attached and free‐living MGIIs. A nearly completely assembled metagenome, MGIIa_P, was recovered using metagenome binning methods. Compared with the other two MGII genomes from surface ocean, MGIIa_P contained higher proportions of glycoside hydrolases, indicating the ability of MGIIa_P to hydrolyse glycosidic bonds in complex sugars in PRE. MGIIa_P is the first assembled MGII metagenome containing a catalase gene, which might be involved in scavenging reactive oxygen species generated by the abundant phototrophs in the eutrophic PRE. Our study presented the widespread and high abundance of MGII in the water columns of PRE, and characterized the determinant abiotic factors affecting their distribution. Their association with heterotrophs, preference for particles and resourceful metabolic traits indicate MGII might play a significant role in metabolising organic matters in the PRE and other temperate estuarine systems.

Low mtDNA variation and shallow population structure of the Chinese pomfret Pampus chinensis along the China coast - P. Sun; B. J. Tang (Journal of Fish Biology, 2018)
In the present study, population genetic structure and genetic diversity of the Chinese pomfret Pampus chinensis , along the China coast were investigated and compared with that from Indonesia using mitochondrial DNA cytochrome b gene sequences. A total of 28 variable sites (including 18 singleton sites and 10 parsimony information sites) were observed and 23 haplotypes were defined in 330 individuals from 11 localities. The haplotype diversity ( H D ) of the populations ranged from 0·540 to 0·828, the nucleotide diversity ( π ) ranged from 0·081 to 0·295%. Pairwise F ST statistics showed that significant genetic divergence occurred among populations from different geographical regions. The high dispersal capabilities, geographic segregation and ocean currents may be responsible for the present population genetic structure in this species. In addition, a population expansion event during the late Pleistocene period was inferred. The time of population expansion was estimated to occur about 117 000–169 000 years ago.

In vitro Approaches to Support Bioequivalence and Substitutability of Generic Proton Pump Inhibitors via Nasogastric Tube Administration - Ping Ren; Minglei Cui; Om Anand; Li Xia; Zhuojun J. Zhao; Dajun Sun; Trueman Sharp; Dale P. Conner; John Peters; Wenlei Jiang; Ethan Stier; Xiaojian Jiang (The AAPS Journal, 2017)

ENSO-induced drought hazards and wet spells and related agricultural losses across Anhui province, China - Peng Sun; Qiang Zhang; Chen Cheng; Vijay P. Singh; Peijun Shi (Natural Hazards, 2017)

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Transitional variations and risk of hydro-meteorological droughts in the Tarim River basin, China - Peng Sun; Qiang Zhang; Vijay P. Singh; Mingzhong Xiao; Xiuyu Zhang (Stochastic Environmental Research and Risk Assessment, 2017)

Quality assessment of groundwater from the south-eastern Arabian Peninsula - H. W. Zhang; Y. Q. Sun; Y. Li; X. D. Zhou; X. Z. Tang; P. Yi; A. Murad; S. Hussein; D. Alshamsi; A. Aldahan; Z. B. Yu; X. G. Chen; et al. (Environmental Monitoring and Assessment, 2017)

Co-seismic multilayer water temperature and water level changes associated with Wenchuan and Tohoku-Oki earthquakes in the Chuan no. 03 well, China - Anhua He; Gang Zhao; Zhaohua Sun; Ramesh P. Singh (Journal of Seismology, 2017)

Inhibition of Blood-Brain Barrier Disruption by an Apolipoprotein E-Mimetic Peptide Ameliorates Early Brain Injury in Experimental Subarachnoid Hemorrhage - Jinwei Pang; Yitian Chen; Li Kuai; Ping Yang; Jianhua Peng; Yue Wu; Yue Chen; Michael P. Vitek; Ligang Chen; Xiaochuan Sun; Yong Jiang (Translational Stroke Research, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

An assessment of the atmospheric centers of action in the northern hemisphere winter - X. J. Sun; P. X. Wang; J. X. L. Wang (Climate Dynamics, 2017)

On the Mechanics of Transcatheter Aortic Valve Replacement - Lakshmi P. Dasi; Hoda Hatoum; Arash Kheradvar; Ramin Zareian; S. Hamed Alavi; Wei Sun; Caitlin Martin; Thuy Pham; Qian Wang; Prem A. Midha; Vrishank Raghav; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2017)

Evaluation of transitional behavior of wetness/drought regimes in the Poyang Lake Basin, China - Qiang Zhang; Peng Sun; Vijay P. Singh; Jianfeng Li; Xinjun Tu (Theoretical and Applied Climatology, 2016)

Removing Cardiac Artefacts in Magnetoencephalography with Resampled Moving Average Subtraction - Limin Sun; Seppo P. Ahlfors; Hermann Hinrichs (Brain Topography, 2016)

Alterations of Blood Flow Through Arteries Following Atherectomy and the Impact on Pressure Variation and Velocity - Brian D. Plourde; Lauren J. Vallez; Biyuan Sun; Brittany B. Nelson-Cheeseman; John P. Abraham; Cezar S. Staniloae (Cardiovascular Engineering and Technology, 2016)

Linking morphological and functional variability in hand movement and silent reading - Z. Y. Sun; P. Pinel; D. Rivière; A. Moreno; S. Dehaene; J.-F. Mangin (Brain Structure and Function, 2016)

Effect of Selenium Against Lead-Induced Damage on the Gene Expression of Heat Shock Proteins and Inflammatory Cytokines in Peripheral Blood Lymphocytes of Chickens - G.X. Sun; Y. Chen; C. P. Liu; S. Li; J. Fu (Biological Trace Element Research, 2016)

Comparison of Regression Methods to Compute Atmospheric Pressure and Earth Tidal Coefficients in Water Level Associated with Wenchuan Earthquake of 12 May 2008 - Anhua He; Ramesh P. Singh; Zhaohua Sun; Qing Ye; Gang Zhao (Pure and Applied Geophysics, 2016)

Natural isoforms of the Photosystem II D1 subunit differ in photoassembly efficiency of the water-oxidizing complex - David J. Vinyard; Jennifer S. Sun; Javier Gimpel; Gennady M. Ananyev; Stephen P. Mayfield; G. Charles Dismukes (Photosynthesis Research, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Uptake of 2,4-bis(Isopropylamino)-6-methylthio-s-triazine by Vetiver Grass (Chrysopogon zizanioides L.) from Hydroponic Media - S. X. Sun; Y. M. Li; Y. Zheng; Y. Hua; R. Datta; Y. M. Dan; P. Lv; D. Sarkar (Bulletin of Environmental Contamination and Toxicology, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Rock Cavern Stability Analysis Under Different Hydro-Geological Conditions Using the Coupled Hydro-Mechanical Model - H. M. Chen; Z. Y. Zhao; L. Q. Choo; J. P. Sun (Rock Mechanics and Rock Engineering, 2016)

Simulation of Asymmetric Destabilization of Mine-void Rock Masses Using a Large 3D Physical Model - X. P. Lai; P. F. Shan; J. T. Cao; F. Cui; H. Sun (Rock Mechanics and Rock Engineering, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Evaluation of environmental friendliness of concrete paving eco-blocks using LCA approach - Md. Uzzal Hossain; Chi Sun Poon; Irene M. C. Lo; Jack C. P. Cheng (The International Journal of Life Cycle Assessment, 2016)

Observed changes in the Earth’s dynamic oblateness from GRACE data and geophysical models - Y. Sun; P. Ditmar; R. Riva (Journal of Geodesy, 2016)

Trimeric autotransporter adhesins contribute to Actinobacillus pleuropneumoniae pathogenicity in mice and regulate bacterial gene expression during interactions between bacteria and porcine primary alveolar macrophages - Wanhai Qin; Lei Wang; Ruidong Zhai; Qiuyue Ma; Jianfang Liu; Chuntong Bao; Hu Zhang; Changjiang Sun; Xin Feng; Jingmin Gu; Chongtao Du; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2016)

Risk factors for young-onset invasive and in situ breast cancer - Katie M. O’Brien; Jenny Sun; Dale P. Sandler; Lisa A. DeRoo; Clarice R. Weinberg (Cancer Causes & Control, 2015)

In vitro and in vivo single myosin step-sizes in striated muscle - Thomas P. Burghardt; Xiaojing Sun; Yihua Wang; Katalin Ajtai (Journal of Muscle Research and Cell Motility, 2015)

Translational biomarkers of acetaminophen-induced acute liver injury - Richard D. Beger; Sudeepa Bhattacharyya; Xi Yang; Pritmohinder S. Gill; Laura K. Schnackenberg; Jinchun Sun; Laura P. James (Archives of Toxicology, 2015)

Responses to increases in temperature of heterotrophic micro-organisms in soils from the maritime Antarctic - Vito Armando Laudicina; Sun Benhua; Paul G. Dennis; Luigi Badalucco; Steven P. Rushton; Kevin K. Newsham; Anthony G. O’Donnell; Iain P. Hartley; David W. Hopkins (Polar Biology, 2015)

Assessment of drought vulnerability of the Tarim River basin, Xinjiang, China - Qiang Zhang; Peng Sun; Jianfeng Li; Mingzhong Xiao; Vijay P. Singh (Theoretical and Applied Climatology, 2015)

Electrophysiological Differences between the Same Pore Region Mutation in SCN1A and SCN3A - Y.-J. Chen; Y.-W. Shi; H.-Q. Xu; M.-L. Chen; M.-M. Gao; W.-W. Sun; B. Tang; Y. Zeng; W.-P. Liao (Molecular Neurobiology, 2015)

Differential Roles of the Mevalonate Pathway in the Development and Survival of Mouse Purkinje Cells in Culture - Andrew Barszczyk; Hong-Shuo Sun; Yi Quan; Wenhua Zheng; Milton P. Charlton; Zhong-Ping Feng (Molecular Neurobiology, 2015)

Measurement of slow-moving along-track displacement from an efficient multiple-aperture SAR interferometry (MAI) stacking - Min-Jeong Jo; Hyung-Sup Jung; Joong-Sun Won; Michael P. Poland; Asta Miklius; Zhong Lu (Journal of Geodesy, 2015)

Strategies to Maximize Liposomal Drug Loading for a Poorly Water-soluble Anticancer Drug - Wenli Zhang; Guangji Wang; James R. Falconer; Bruce C. Baguley; John P. Shaw; Jianping Liu; Hongtao Xu; Esther See; Jianguo Sun; Jiye Aa; Zimei Wu (Pharmaceutical Research, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

A Matérn model of the spatial covariance structure of point rain rates - Ying Sun; Kenneth P. Bowman; Marc G. Genton; Ali Tokay (Stochastic Environmental Research and Risk Assessment, 2015)

The association of previously reported polymorphisms for microvascular complications in a meta-analysis of diabetic retinopathy - S. Mohsen Hosseini; Andrew P. Boright; Lei Sun; Angelo J. Canty; Shelley B. Bull; Barbara E. K. Klein; Ronald Klein; Andrew D. Paterson (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Deep-Sea Nodules and Co-rich Mn Crusts - G. P. Glasby; Jun Li; Zhilei Sun (Marine Georesources & Geotechnology, 2015)

Splenic necrosis signs and pathogen detection in cultured half‐smooth tongue sole, Cynoglossus semilaevis Günther - P Xiao; M Jiang; Y Liu; M Sun; L Zhang; L Jie; G Li; Z Mo (Journal of Fish Diseases, 2015)

Continuous flow left ventricular pump support and its effect on regional left ventricular wall stress: finite element analysis study - Choon-Sik Jhun; Kay Sun; Joshua P. Cysyk (Medical & Biological Engineering & Computing, 2014)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Development of Rock Bolt Elements in Two-Dimensional Discontinuous Deformation Analysis - W. Nie; Z. Y. Zhao; Y. J. Ning; J. P. Sun (Rock Mechanics and Rock Engineering, 2014)

Effect of polymorphisms in the CSN3 (κ-casein) gene on milk production traits in Chinese Holstein Cattle - M. A. Alim; T. Dong; Y. Xie; X. P. Wu; Yi Zhang; Shengli Zhang; D. X. Sun (Molecular Biology Reports, 2014)

A rapid ex vivo tissue model for optimising drug detection and ionisation in MALDI imaging studies - K. Huber; M. Aichler; N. Sun; A. Buck; Z. Li; I. E. Fernandez; S. M. Hauck; H. Zitzelsberger; O. Eickelberg; K. P. Janssen; U. Keller; A. Walch (Histochemistry and Cell Biology, 2014)

Effect of Manure Treatment on Ammonia Emission during Storage under Ambient Environment - F. Sun; J. H. Harrison; P. M. Ndegwa; K. Johnson (Water, Air, & Soil Pollution, 2014)

Risk factors for bacterial vaginosis: results from a cross-sectional study having a sample of 53,652 women - X.-D. Li; C.-C. Wang; X.-J. Zhang; G.-P. Gao; F. Tong; X. Li; S. Hou; L. Sun; Y.-H. Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A region of euchromatin coincides with an extensive tandem repeat on the mouse (Mus musculus) inactive X chromosome - Emily M. Darrow; Andrew P. Seberg; Sunny Das; Debbie M. Figueroa; Zhuo Sun; Shawn C. Moseley; Brian P. Chadwick (Chromosome Research, 2014)

Proteomic analysis of meningiomas - G. Q. Cui; A. H. Jiao; C. M. Xiu; Y. B. Wang; P. Sun; L. M. Zhang; X. G. Li (Acta Neurologica Belgica, 2014)

Cellular Membrane Fluidity in Amyloid Precursor Protein Processing - Xiaoguang Yang; Grace Y. Sun; Gunter P. Eckert; James C-M. Lee (Molecular Neurobiology, 2014)

A double-blind comparative study of Chinese herbal medicine Jinlianqingre Effervescent Tablets in combination with conventional therapy for the treatment of uncomplicated hand, foot, and mouth disease - L.-Y. He; G.-L. Zhang; S.-Y. Yan; Y. Liu; C.-S. Zhao; X.-L. Wang; Y. Li; Y.-Q. Mi; Y.-M. Liu; C.-P. Li; Y.-H. Kou; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of Manure Treatment on Ammonia and Greenhouse Gases Emissions Following Surface Application - F. Sun; J. H. Harrison; P. M. Ndegwa; K. Johnson (Water, Air, & Soil Pollution, 2014)

A novel rhizobacterium Bk7 for biological control of brown sheath rot of rice caused by Pseudomonas fuscovaginae and its mode of action - Kaleem Ullah Kakar; Y.-P. Duan; Zarqa Nawaz; Guochang Sun; Abdlwareth A. Almoneafy; M. Auwal Hassan; Ahmed Elshakh; Bin Li; Guan-Lin Xie (European Journal of Plant Pathology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Mapping quantitative trait loci (QTL) for body weight, length and condition factor traits in backcross (BC1) family of Common carp (Cyprinus carpio L.) - M. Y. Laghari; P. Lashari; X. Zhang; P. Xu; B. Xin; Y. Zhang; N. T. Narejo; X. Sun (Molecular Biology Reports, 2014)

Late Quaternary Qaidam lake histories and implications for an MIS 3 “Greatest Lakes” period in northwest China - David B. Madsen; ZhongPing Lai; YongJuan Sun; David Rhode; XiangJun Liu; P. Jeffrey Brantingham (Journal of Paleolimnology, 2014)

Influence of an Inclined Rock Stratum on In-Situ Stress State in an Open-Pit Mine - Wenhui Tan; P. H. S. W. Kulatilake; Hongbao Sun (Geotechnical and Geological Engineering, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Photoheterotrophic growth unprecedentedly increases the biosynthesis of mycosporine-like amino acid shinorine in the cyanobacterium Anabaena sp., isolated from hot springs of Rajgir (India) - Shailendra P. Singh; Sun-yong Ha; Rajeshwar P. Sinha; Donat-P. Häder (Acta Physiologiae Plantarum, 2014)

CpG methylation of dmrt1 and cyp19a promoters in relation to their sexual dimorphic expression in the Japanese flounder Paralichthys olivaceus - A. Y. Wen; F. You; P. Sun; J. Li; D. D. Xu; Z. H. Wu; D. Y. Ma; P. J. Zhang (Journal of Fish Biology, 2014)
To better understand the effects of DNA methylation on the expression patterns of dmrt1 (Doublesex and Mab‐3‐related transcription factor 1) and cyp19a (Cytochrome P450 19a) in the Japanese flounder Paralichthys olivaceus , quantitative expressions, cellular distributions and cytosine‐p‐guanine (CpG) methylation patterns of these two genes in the gonads were analysed. The results showed that P. olivaceus dmrt1 expression was 70 times higher in the testis than in the ovary ( P mRNA was detected clearly in spermatocytes and Sertoli cells of the testis, but weakly in the ovary. Paralichthys olivaceus cyp19a expression was 40 times higher in the ovary than in the testis ( P mRNA was detected clearly in follicular cells of the ovary, but weakly in spermatocytes of the testis. The dmrt1 promoter CpGs were not methylated in the testis, whereas 57·69% were methylated in the ovary. For the cyp19a promoter CpGs , 97·5% were methylated in the testis and 73·33% were methylated in the ovary. These findings demonstrate that P. olivaceus dmrt1 and cyp19a are sex‐related genes with sexual dimorphic expression, CpG methylation levels of the two genes are consistent with their expression quantities, and this epigenetic modification can influence the differential expression of genes in the gonads of P. olivaceus .

Clinical and epidemiological survey and analysis of the first case of human infection with avian influenza A(H7N9) virus in Hangzhou, China - L. Xie; H. Ding; Q.-J. Kao; X.-H. Yang; Y.-Y. Wen; H.-K. Lv; Z.-P. Chen; E.-F. Chen; Z. Sun; J.-C. Pan; X.-Y. Pu; J. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Sensitivity of large-scale vegetation greenup and dormancy dates to climate change in the north−south transect of eastern China - Z. Yu; P. Sun; S. Liu; J. Wang; A. Everman (International Journal of Remote Sensing, 2013)

Experimental study on cascading landslide dam failures by upstream flows - Gordon G. D. Zhou; P. Cui; H. Y. Chen; X. H. Zhu; J. B. Tang; Q. C. Sun (Landslides, 2013)

Transcriptome analyses of Arabidopsis thaliana seedlings grown in space: implications for gravity-responsive genes - Melanie J. Correll; Tyler P. Pyle; Katherine D. L. Millar; Yijun Sun; Jin Yao; Richard E. Edelmann; John Z. Kiss (Planta, 2013)

Regulation of phenylalanine ammonia-lyase (PAL) gene family in wood forming tissue of Populus trichocarpa - Rui Shi; Christopher M. Shuford; Jack P. Wang; Ying-Hsuan Sun; Zhichang Yang; Hsi-Chuan Chen; Sermsawat Tunlaya-Anukit; Quanzi Li; Jie Liu; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2013)

QTL analysis of the spring wheat “Chapio” identifies stable stripe rust resistance despite inter-continental genotype × environment interactions - E.-N. Yang; G. M. Rosewarne; S. A. Herrera-Foessel; J. Huerta-Espino; Z.-X. Tang; C.-F. Sun; Z.-L. Ren; R. P. Singh (Theoretical and Applied Genetics, 2013)

Inexact quadratic joint-probabilistic programming for water quality management under uncertainty in the Xiangxi River, China - Ming Hu; Guo H. Huang; Wei Sun; Yongping P. Li (Stochastic Environmental Research and Risk Assessment, 2013)

Development of a placebo effect model combined with a dropout model for bipolar disorder - Wan Sun; Thomas P. Laughren; Hao Zhu; Guenther Hochhaus; Yaning Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2013)

Temporal Variability of Water Footprint for Maize Production: The Case of Beijing from 1978 to 2008 - S. K. Sun; P. T. Wu; Y. B. Wang; X. N. Zhao (Water Resources Management, 2013)

Identification of a novel bluetongue virus 1-specific B-cell epitope using a monoclonal antibody against the VP2 protein - P. Wei; E. C. Sun; N. H. Liu; T. Yang; Q. Y. Xu; J. Zhao; Y. L. Qin; Y. F. Feng; J. P. Li; W. S. Wang; C. Y. Zhang; D. L. Wu (Archives of Virology, 2013)

The effects of molybdenum and boron on the rhizosphere microorganisms and soil enzyme activities of soybean - Ting Sun; Yue P. Wang; Zhi Y. Wang; Peng Liu; Gen D. Xu (Acta Physiologiae Plantarum, 2013)

Primary genome scan for complex body shape‐related traits in the common carp Cyprinus carpio - Y. Zhang; S. Wang; J. Li; X. Zhang; L. Jiang; P. Xu; C. Lu; Y. Wan; X. Sun (Journal of Fish Biology, 2013)
To identify quantitative trait loci (QTL) that affect body shape in common carp Cyprinus carpio , a linkage map, 2159·23 cM long, was constructed with a total of 307 markers covering 51 linkage groups (LG). The map included 167 new single nucleotide polymorphism (SNP) markers derived from expressed sequence tags (EST) together with 140 microsatellite markers reported earlier. A primary genome scan was conducted for QTL for standard length ( L S ), head length ( L H ), body height ( H B ), body width ( W B ) and tail length ( L TAIL ) in an F1 line containing 92 offspring. A total of 15 suggestive QTL on six LGs were found to associate with L S , L H , H B , W B and L TAIL which explained 10·7–17·4% of the variance. Five significant QTL were detected for body‐shape related traits and located for LGs ( lg1 , 12 and 20 ). These QTL included: one associated with L S (21·1% variance explained), three for H B (almost 20% variance explained) and one for W B (20·7% variance explained).

The effects of parasites on the early life stages of a damselfish - D. Sun; S. P. Blomberg; T. H. Cribb; M. I. McCormick; A. S. Grutter (Coral Reefs, 2012)

Multiblock Pore-Scale Modeling and Upscaling of Reactive Transport: Application to Carbon Sequestration - Y. Mehmani; T. Sun; M. T. Balhoff; P. Eichhubl; S. Bryant (Transport in Porous Media, 2012)

Phospho-Sulindac (OXT-328) Inhibits the Growth of Human Lung Cancer Xenografts in Mice: Enhanced Efficacy and Mitochondria Targeting by its Formulation in Solid Lipid Nanoparticles - Rongrong Zhu; Ka-Wing Cheng; Gerardo Mackenzie; Liqun Huang; Yu Sun; Gang Xie; Kveta Vrankova; Panayiotis P. Constantinides; Basil Rigas (Pharmaceutical Research, 2012)

Adoptive immunity mediated by HLA-A*0201 restricted Asp f16 peptides-specific CD8+ T cells against Aspergillus fumigatus infection - Z. Sun; P. Zhu; L. Li; Z. Wan; Z. Zhao; R. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Isolation and characterization of Viviparous-1 haplotypes in wheat related species - Y. W. Sun; Y. Yang; P. R. Shewry; H. D. Jones; L. Q. Xia (Euphytica, 2012)

CTCF and Sp1 interact with the Murine gammaherpesvirus 68 internal repeat elements - Hannah C. Stevens; Kevin S-W Cham; David J. Hughes; Ren Sun; Jeffery T. Sample; Vivien J. Bubb; James P. Stewart; John P. Quinn (Virus Genes, 2012)

Intracellular-signaling tumor-regression modeling of the pro-apoptotic receptor agonists dulanermin and conatumumab - Brittany P. Kay; Cheng-Pang Hsu; Jian-Feng Lu; Yu-Nien Sun; Shuang Bai; Yan Xin; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Collaborative Gaze Channelling for Improved Cooperation During Robotic Assisted Surgery - Ka-Wai Kwok; Loi-Wah Sun; George P. Mylonas; David R. C. James; Felipe Orihuela-Espina; Guang-Zhong Yang (Annals of Biomedical Engineering, 2012)

Paradigm Shift in Toxicity Testing and Modeling - Hongmao Sun; Menghang Xia; Christopher P. Austin; Ruili Huang (The AAPS Journal, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Genetic effects of stearoyl-coenzyme A desaturase (SCD) polymorphism on milk production traits in the Chinese dairy population - M. A. Alim; Y. P. Fan; X. P. Wu; Y. Xie; Y. Zhang; S. L. Zhang; D. X. Sun; Y. Zhang; Q. Zhang; L. Liu; G. Guo (Molecular Biology Reports, 2012)

Utility of in vitro culture to the study of plant mitochondrial genome configuration and its dynamic features - Peibei Sun; Maria P. Arrieta-Montiel; Sally A. Mackenzie (Theoretical and Applied Genetics, 2012)

Natural epigenetic variation in the female great roundleaf bat (Hipposideros armiger) populations - Sen Liu; Keping Sun; Tinglei Jiang; Jennifer P. Ho; Bao Liu; Jiang Feng (Molecular Genetics and Genomics, 2012)

Foreword - Walter E. Müller; Gunter P. Eckert; Grace Y. Sun; W. Gibson Wood (Molecular Neurobiology, 2012)

The key role of PGC-1α in mitochondrial biogenesis and the proliferation of pulmonary artery vascular smooth muscle cells at an early stage of hypoxic exposure - Jingjing Rao; Jing Li; Yun Liu; Ping Lu; Xiaojiao Sun; P. K. Sugumaran; Daling Zhu (Molecular and Cellular Biochemistry, 2012)

Managing water resources system in a mixed inexact environment using superiority and inferiority measures - Y. Lv; G. H. Huang; Y. P. Li; W. Sun (Stochastic Environmental Research and Risk Assessment, 2012)

Haplotype analysis of Viviparous-1 gene in CIMMYT elite bread wheat germplasm - Y. W. Sun; H. D. Jones; Y. Yang; S. Dreisigacker; S. M. Li; X. M. Chen; P. R. Shewry; L. Q. Xia (Euphytica, 2012)

Effect of poly‐β‐hydroxybutyrate on Chinese mitten crab, Eriocheir sinensis , larvae challenged with pathogenic Vibrio anguillarum - L Sui; J Cai; H Sun; M Wille; P Bossier (Journal of Fish Diseases, 2012)
This study investigated the protective effect of poly‐β‐hydroxybutyrate (PHB) on Chinese mitten crab, Eriocheir sinensis, zoea larvae challenged with pathogenic Vibrio anguillarum . PHB was delivered to the crab larvae through rotifer and Artemia bioencapsulation. Zoea 3 larvae were challenged with V. anguillarum at a final concentration of 10 5 CFU mL −1 . PHB‐enriched rotifers and Artemia nauplii were added to the culture water 24 h prior to, upon and 24 h after challenge. The results confirmed that PHB could enhance the survival and growth of unexposed E. sinensis larvae. Moreover, PHB protected larvae from the pathogen as the larvae fed PHB‐enriched live food showed the highest survival and development rate in all challenged groups ( P P E. sinensis larvae from V. anguillarum resulting in higher survival and better growth, especially when applied before the challenge.

A simple calibration improved the accuracy of the thermal dissipation technique for sap flow measurements in juvenile trees of six species - Huizhen Sun; Doug P. Aubrey; Robert O. Teskey (Trees, 2012)

An approach to quantify the heat wave strength and price a heat derivative for risk hedging - Samuel S. P. Shen; Benedikt Kramps; Shirley X. Sun; Barbara Bailey (Advances in Atmospheric Sciences, 2012)

Bacterial community transcription patterns during a marine phytoplankton bloom - Johanna M. Rinta‐Kanto; Shulei Sun; Shalabh Sharma; Ronald P. Kiene; Mary Ann Moran (Environmental Microbiology, 2012)
Summary Bacterioplankton consume a large proportion of photosynthetically fixed carbon in the ocean and control its biogeochemical fate. We used an experimental metatranscriptomics approach to compare bacterial activities that route energy and nutrients during a phytoplankton bloom compared with non‐bloom conditions. mRNAs were sequenced from duplicate bloom and control microcosms 1 day after a phytoplankton biomass peak, and transcript copies per litre of seawater were calculated using an internal mRNA standard. Transcriptome analysis revealed a potential novel mechanism for enhanced efficiency during carbon‐limited growth, mediated through membrane‐bound pyrophosphatases [V‐type H(+)‐translocating; hppA ]; bloom bacterioplankton participated less in this metabolic energy scavenging than non‐bloom bacterioplankton, with possible implications for differences in growth yields on organic substrates. Bloom bacterioplankton transcribed more copies of genes predicted to increase cell surface adhesiveness, mediated by changes in bacterial signalling molecules related to biofilm formation and motility; these may be important in microbial aggregate formation. Bloom bacterioplankton also transcribed more copies of genes for organic acid utilization, suggesting an increased importance of this compound class in the bioreactive organic matter released during phytoplankton blooms. Transcription patterns were surprisingly faithful within a taxon regardless of treatment, suggesting that phylogeny broadly predicts the ecological roles of bacterial groups across ‘boom’ and ‘bust’ environmental backgrounds.

Evolution of attenuating mutations in dengue-2 strain S16803 PDK50 vaccine and comparison of growth kinetics with parent virus - Eileen P. Kelly; Stephanie Polo; Wellington Sun; Barry Falgout (Virus Genes, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Probabilistic acute dietary exposure assessment of the Chinese population to cypermethrin residues - J.-F. Sun; P. Liu; C.-Y. Li; J.-X. Li; C.-N. Wang; J. Min; D. Hu; Y.-N. Wu (Food Additives & Contaminants: Part A, 2011)

Bioactive Electrospun Scaffolds Delivering Growth Factors and Genes for Tissue Engineering Applications - Wei Ji; Yan Sun; Fang Yang; Jeroen J. J. P. van den Beucken; Mingwen Fan; Zhi Chen; John A. Jansen (Pharmaceutical Research, 2011)

Cultural heritage: a potential pollution source in museum - CheolMin Lee; YoonShin Kim; P. C. Nagajyothi; Soulighothai Thammalangsy; Sun Ju Nam Goung (Environmental Science and Pollution Research, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Calculation of the dietary exposure of Chinese consumers to acephate residues using deterministic and probabilistic approaches - P. Liu; C.-Y. Li; C.-N. Wang; J.-F. Sun; J. Min; D. Hu; Y.-N. Wu (Food Additives & Contaminants: Part A, 2011)

Effect of dietary HUFA on tissue fatty acid composition and reproductive performance of Chinese mitten crab Eriocheir sinensis (H. Milne-Edwards) broodstock - L. Y. Sui; H. X. Sun; X. G. Wu; M. Wille; Y. X. Cheng; P. Sorgeloos (Aquaculture International, 2011)

Ethics Consultation on a Gynecologic Oncology Service: An Opportunity for Physician Education - Matthew P. Schlumbrecht; Colleen M. Gallagher; Charlotte C. Sun; Lois M. Ramondetta; Diane C. Bodurka (Journal of Cancer Education, 2011)

Atmospheric Stability Effects on Wind Fields and Scalar Mixing Within and Just Above a Subalpine Forest in Sloping Terrain - Sean P. Burns; Jielun Sun; Donald H. Lenschow; Steven P. Oncley; Britton B. Stephens; Chuixiang Yi; Dean E. Anderson; Jia Hu; Russell K. Monson (Boundary-Layer Meteorology, 2011)

Analysis of sulfur‐related transcription by Roseobacter communities using a taxon‐specific functional gene microarray - Johanna M. Rinta‐Kanto; Helmut Bürgmann; Scott M. Gifford; Shulei Sun; Shalabh Sharma; Daniela A. del Valle; Ronald P. Kiene; Mary Ann Moran (Environmental Microbiology, 2011)
Summary The fraction of dissolved dimethylsulfoniopropionate (DMSPd) converted by marine bacterioplankton into the climate‐active gas dimethylsulfide (DMS) varies widely in the ocean, with the factors that determine this value still largely unknown. One current hypothesis is that the ratio of DMS formation : DMSP demethylation is determined by DMSP availability, with ‘availability’ in both an absolute sense (i.e. concentration in seawater) and in a relative sense (i.e. proportionally to other labile organic S compounds) proposed as the critical factor. We investigated these models during an experimentally induced phytoplankton bloom using a taxon‐specific microarray targeting DMSP‐related gene transcription in members of the Roseobacter clade, a group hypothesized to play an important role in the surface ocean sulfur cycle and well represented by genome sequences. The array consisted of 1578 probes to 431 genes and was designed to target diverse Roseobacter communities in natural seawater by using hierarchical probe design based on 13 genome sequences. The prevailing pattern of Roseobacter gene transcription showed relative depletion of DMSP‐related transcripts during the peak of the bloom, despite increasing absolute concentrations and flux of DMSP‐related compounds. DMSPd thus appeared to be assimilated by Roseobacter populations in proportion to its relative abundance in the organic matter pool (the ‘relative sense’ hypothesis), rather than assimilated in preference to other labile organic sulfur or carbon compounds produced during the bloom. The relative investment of the Roseobacter community in DMSP demethylation was not useful for predicting the formation of DMS, however, suggesting a complex regulatory process that may involve multiple taxa and alternative fates of DMSPd.

Long-term dietary exposure to lead of the population of Jiangsu Province, China - J.-F. Sun; C.-N. Wang; Y.-N. Wu; B.-J. Yuan; Z.-H. Tian; X.-Y. Song; C.-Y. Li; P. Liu (Food Additives & Contaminants: Part A, 2011)

First record of three giant marine Bathynomids (Crustacea, Isopoda, Cirolanidae) from India - R. Sankar; M. Rajkumar; Jun Sun; A. Gopalakrishnan; T. M. Vasanthan; G. Ananthan; J. P. Trilles (Acta Oceanologica Sinica, 2011)

An Impact Assessment Method of Dam/Sluice on Instream Ecosystem and its Application to the Bengbu Sluice of China - C. S. Zhao; C. L. Sun; J. Xia; X. P. Hao; G. F. Li; K. Rebensburg; C. M. Liu (Water Resources Management, 2010)

Biodiversity of brackish water amphipods (crustacean) in two estuaries, southeast coast of India - Nityananda Mondal; Mayalagu Rajkumar; Jun Sun; Sourav Kundu; P. S. Lyla; Seyed Ajmal Khan; Jean Paul Trilles (Environmental Monitoring and Assessment, 2010)

Polymorphic microsatellite loci for the threatened Xantus’s Murrelet (Synthliboramphus hypoleucus scrippsi) - Tim P. Birt; Zhengxin Sun; Harry R. Carter; Darrell L. Whitworth; Scott H. Newman; Vicki L. Friesen (Conservation Genetics Resources, 2010)

Bloom forming species of phytoplankton in two coastal waters in the Southeast coast of India - K. Thillai Rajasekar; M. Rajkumar; Jun Sun; V. Ashok Prabu; P. Perumal (Journal of Ocean University of China, 2010)

Seasonal variations of phytoplankton diversity in the Coleroon coastal waters, southeast coast of India - Rajasekar K. Thillai; M. Rajkumar; Jun Sun; Prabu V. Ashok; P. Perumal (Acta Oceanologica Sinica, 2010)

Comparative study of serology and histology based detection of Helicobacter pylori infections: a large population-based study of 7,241 subjects from China - Y. H. Gong; L. P. Sun; S. G. Jin; Y. Yuan (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Identification and characterization of PshBII, a second FA/FB-containing polypeptide in the photosynthetic reaction center of Heliobacterium modesticaldum - Steven P. Romberger; Christian Castro; Yili Sun; John H. Golbeck (Photosynthesis Research, 2010)

Simvastatin Stimulates Production of the Antiapoptotic Protein Bcl-2 via Endothelin-1 and NFATc3 in SH-SY5Y Cells - Tammy A. Butterick; Urule Igbavboa; Gunter P. Eckert; Grace Y. Sun; Gary A. Weisman; Walter E. Müller; W. Gibson Wood (Molecular Neurobiology, 2010)

Identification and characterization of the dominant lactic acid bacteria isolated from traditional fermented milk in Mongolia - Z. H. Sun; W. J. Liu; J. C. Zhang; J. Yu; W. Gao; M. Jiri; B. Menghe; T. S. Sun; H. P. Zhang (Folia Microbiologica, 2010)

Spatiotemporal modeling of monthly precipitation in the upper Shiyang River watershed in west central Gansu, northwest China - Cunjie Zhang; C. P. -A. Bourque; Landong Sun; Q. K. Hassan (Advances in Atmospheric Sciences, 2010)

Frequencies of killer immunoglobulin-like receptor genotypes influence susceptibility to spontaneous abortion - I. Nowak; A. Malinowski; H. Tchórzewski; E. Barcz; J. R. Wilczyński; M. Gryboś; M. Kurpisz; W. Łuszczek; M. Banasik; D. Reszczyńska-Ślęzak; E. Majorczyk; A. Wiśniewski; et al. (Journal of Applied Genetics, 2009)

Development and characterization of microsatellite markers to study population genetic diversity of Przewalski's naked carp Gymnocypris przewalskii in China - Y. Zhang; P. Jiang; H. Gang; J.‐Q. Shi; X. Sun (Journal of Fish Biology, 2009)
Two populations of Przewalski's naked carp Gymnocypris przewalskii , 30 individuals per population, were screened for 10 microsatellite loci. Moderate allele variation was found in these loci with two to eight alleles per locus. The expected and observed heterozygosity ranged from 0·019 to 0·805 and from 0·160 to 0·575, respectively.

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Study on blood cultures and bacteria counts in the blood of paratyphoid fever A patients - S. K. Wang; C. J. Chu; P. S. Sun; D. S. Shan; F. L. Kong; H. Y. Liu; Q. Wu; R. S. Yang; Y. B. Yao (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Endocrine-disrupting equivalents in industrial effluents discharged into Yangtze River - Wei Shi; Xiaoyi Wang; Wei Hu; Hong Sun; Ouxi Shen; Hongling Liu; Xinru Wang; John P. Giesy; Shupei Cheng; Hongxia Yu (Ecotoxicology, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Purified Recombinant Phage Lysin LySMP: An Extensive Spectrum of Lytic Activity for Swine Streptococci - Y. Wang; J. H. Sun; C. P. Lu (Current Microbiology, 2009)

Comparative day/night metatranscriptomic analysis of microbial communities in the North Pacific subtropical gyre - Rachel S. Poretsky; Ian Hewson; Shulei Sun; Andrew E. Allen; Jonathan P. Zehr; Mary Ann Moran (Environmental Microbiology, 2009)
Summary Metatranscriptomic analyses of microbial assemblages ( Cyanobacteria contributed a greater percentage of the transcripts (54% of annotated sequences) than expected based on abundance (35% of cell counts and 21% 16S rRNA of libraries), and may represent the most actively transcribing cells in this surface ocean community in both the day and night. Major heterotrophic taxa contributing to the community transcriptome included α ‐Proteobacteria (19% of annotated sequences, most of which were SAR11‐related) and γ ‐Proteobacteria (4%). The composition of transcript pools was consistent with models of prokaryotic gene expression, including operon‐based transcription patterns and an abundance of genes predicted to be highly expressed. Metabolic activities that are shared by many microbial taxa (e.g. glycolysis, citric acid cycle, amino acid biosynthesis and transcription and translation machinery) were well represented among the community transcripts. There was an overabundance of transcripts for photosynthesis, C1 metabolism and oxidative phosphorylation in the day compared with night, and evidence that energy acquisition is coordinated with solar radiation levels for both autotrophic and heterotrophic microbes. In contrast, housekeeping activities such as amino acid biosynthesis, membrane synthesis and repair, and vitamin biosynthesis were overrepresented in the night transcriptome. Direct sequencing of these environmental transcripts has provided detailed information on metabolic and biogeochemical responses of a microbial community to solar forcing.

Pollution extents of organic substances from a coal gangue dump of Jiulong Coal Mine, China - Y. Z. Sun; J. S. Fan; P. Qin; H. Y. Niu (Environmental Geochemistry and Health, 2009)

Seasonality of Gyrodactylus brachymystacis Ergens on farmed rainbow trout, Oncorhynchus mykiss (Walbaum), in central China, with a report of an infection on wild Manchurian trout, Brachymystax lenok (Pallas) - P You; Y Wang; X Sun; X Qiang; D Cone (Journal of Fish Diseases, 2008)

Using the vegetation temperature condition index for time series drought occurrence monitoring in the Guanzhong Plain, PR China - W. Sun; P.‐X. Wang; S.‐Y. Zhang; D.‐H. Zhu; J.‐M. Liu; J.‐H. Chen; H.‐S. Yang (International Journal of Remote Sensing, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

An Easier Method for Locating Replication Origins Based on Real-Time Polymerase Chain Reaction - Y. Mei; D. Chen; D. Sun; Y. Yang; Y. Huang; P. Shen; X. Chen (Current Microbiology, 2008)

Associated changes in physiological parameters and spectral reflectance indices in olive ( Olea europaea L.) leaves in response to different levels of water stress - P. Sun; A. Grignetti; S. Liu; R. Casacchia; R. Salvatori; F. Pietrini; F. Loreto; M. Centritto (International Journal of Remote Sensing, 2008)

Silicon isotope fractionation in rice plants, an experimental study on rice growth under hydroponic conditions - L. Sun; L. H. Wu; T. P. Ding; S. H. Tian (Plant and Soil, 2008)

A guanylyl cyclase-like gene is associated with Gibberella ear rot resistance in maize (Zea mays L.) - J. Yuan; M. Liakat Ali; J. Taylor; J. Liu; G. Sun; W. Liu; P. Masilimany; A. Gulati-Sakhuja; K. P. Pauls (Theoretical and Applied Genetics, 2008)

Community composition of ammonia-oxidizing bacteria in the rhizosphere of intercropped wheat (Triticum aestivum L.), maize (Zea mays L.), and faba bean (Vicia faba L.) - Y. N. Song; P. Marschner; L. Li; X. G. Bao; J. H. Sun; F. S. Zhang (Biology and Fertility of Soils, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Genomic analysis of rice stripe virus Zhejiang isolate shows the presence of an OTU-like domain in the RNA1 protein and a novel sequence motif conserved within the intergenic regions of ambisense segments of tenuiviruses - H.-M. Zhang; J. Yang; H.-R. Sun; X. Xin; H.-D. Wang; J.-P. Chen; M. J. Adams (Archives of Virology, 2007)

Simulation of canopy radiation transfer and surface albedo in the EALCO model - Shusen Wang; Alexander P. Trishchenko; Xiaomin Sun (Climate Dynamics, 2007)

Multi‐sensor studies of the Sumatra earthquake and tsunami of 26 December 2004 - R. P. Singh; G. Cervone; M. Kafatos; A. K. Prasad; A. K. Sahoo; D. Sun; D. L. Tang; R. Yang (International Journal of Remote Sensing, 2007)

Allelic variation of polyphenol oxidase (PPO) genes located on chromosomes 2A and 2D and development of functional markers for the PPO genes in common wheat - X. Y. He; Z. H. He; L. P. Zhang; D. J. Sun; C. F. Morris; E. P. Fuerst; X. C. Xia (Theoretical and Applied Genetics, 2007)

Effect of intercropping on crop yield and chemical and microbiological properties in rhizosphere of wheat (Triticum aestivum L.), maize (Zea mays L.), and faba bean (Vicia faba L.) - Y. N. Song; F. S. Zhang; P. Marschner; F. L. Fan; H. M. Gao; X. G. Bao; J. H. Sun; L. Li (Biology and Fertility of Soils, 2007)

Gene structure of an antimicrobial peptide from mandarin fish, Siniperca chuatsi (Basilewsky), suggests that moronecidins and pleurocidins belong in one family: the piscidins - B J Sun; H X Xie; Y Song; P Nie (Journal of Fish Diseases, 2007)
The gene of piscidin, an antimicrobial peptide, has been cloned from the mandarin fish, Siniperca chuatsi . From the first transcription initiation site, the mandarin fish piscidin gene extends 1693 nucleotides to the end of the 3′ untranslated region and contains four exons and three introns. A predicted 79‐residue prepropeptide consists of three domains: a signal peptide (22 aa), a mature peptide (22 aa) and a C‐terminal prodomain (35 aa). The shortage of XQQ motif in the prodomain of mandarin fish piscidin and the similar gene structure between moronecidins (piscidins) and pleurocidins may indicate that they are derived from the same ancestor gene. We thus suggest that piscidin should be used as a terminology for these antimicrobial peptides in the future. The mandarin fish piscidin mRNA was abundant in intestine, spleen, pronephros and kidney analysed by real‐time polymerase chain reaction. After stimulation with lipopoly saccharides (LPS), a marked increase in transcripts was observed in most tissues, indicating that piscidin is not only a constitutively expressed molecule, but also has an increased response to bacterial infection. The synthetic, amidated mandarin fish piscidin exhibited different antimicrobial activity against different fish bacterial pathogens, especially against species of Aeromonas , which may to certain extent reflect the pathogenicity of these bacteria.

Cloning and functional expression of the gene encoding an inhibitor against Aspergillus flavus α-amylase, a novel seed lectin from Lablab purpureus (Dolichos lablab) - Young-Hwa Kim; Charles P. Woloshuk; Eun Hee Cho; Jung Myung Bae; Young-Sun Song; Gyung Hye Huh (Plant Cell Reports, 2007)

A reovirus disease in cultured mud crab, Scylla serrata , in southern China - S‐P Weng; Z‐X Guo; J‐J Sun; S‐M Chan; J‐G He (Journal of Fish Diseases, 2007)
A reovirus, designated mud crab reovirus (MCRV), associated with large economic losses was recently isolated from marine cultured mud crab, Scylla serrata , in southern China. The complete viral particle is 70 nm in diameter, icosahedral and non‐enveloped. The virus infects connective tissue cells of the hepatopancreas, gills and intestine in mud crab and develops in the cytoplasm. Hundred per cent mortality was observed in mud crab experimentally infected by intramuscular injection, bath inoculation and oral inoculation, while cohabitation infection caused 80% mortality. The viral genome consists of 13 linear dsRNA segments, with an electrophoretic pattern 1/5/7. The results of this study suggest that the virus is highly pathogenic and can be transmitted enterically as well as via the body surface of mud crab. Although the genomic organization of this virus is different from that of the other crab reoviruses, CcRV‐W2 and DpPV, all three of these reoviruses have similar electrophoresis patterns. Therefore, MCRV may be a new member of the DpPV and CcRV‐W2 group.

The LRRK2 Gly2385Arg variant is associated with Parkinson’s disease: genetic and functional evidence - E. K. Tan; Y. Zhao; L. Skipper; M. G. Tan; A. Di Fonzo; L. Sun; S. Fook-Chong; S. Tang; E. Chua; Y. Yuen; L. Tan; R. Pavanni; et al. (Human Genetics, 2007)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Inhibition of urease by bismuth(III): Implications for the mechanism of action of bismuth drugs - Li Zhang; Scott B. Mulrooney; Andy F. K. Leung; Yibo Zeng; Ben B. C. Ko; Robert P. Hausinger; Hongzhe Sun (BioMetals, 2006)

Fertility alteration in the photo-thermo-sensitive male sterile line BS20 of wheat (Triticum aestivum L.) - Y. F. Li; C. P. Zhao; F. T. Zhang; H. Sun; D. F. Sun (Euphytica, 2006)

Why is it Challenging to Predict Intestinal Drug Absorption and Oral Bioavailability in Human Using Rat Model - Xianhua Cao; Seth T. Gibbs; Lanyan Fang; Heather A. Miller; Christopher P. Landowski; Ho-Chul Shin; Hans Lennernas; Yanqiang Zhong; Gordon L. Amidon; Lawrence X. Yu; Duxin Sun (Pharmaceutical Research, 2006)

Differences in hepatotoxicity and gene expression profiles by anti-diabetic PPAR γ agonists on rat primary hepatocytes and human HepG2 cells - Lei Guo; Lu Zhang; Yongming Sun; Levan Muskhelishvili; Ernice Blann; Stacey Dial; Leming Shi; Gary Schroth; Yvonne P Dragan (Molecular Diversity, 2006)

Comparison of PAH and nonylphenol Uptake by Carp (Cyprinus carpio) and Semipermeable Membrane Devices (SPMDs) from Water - J. Xu; P. Wang; X. Zhong; S. Dai; H. Sun; Y. Hao (Bulletin of Environmental Contamination and Toxicology, 2006)

Pooled analysis of data from multiple quantitative trait locus mapping populations - B. Guo; D. A. Sleper; J. Sun; H. T. Nguyen; P. R. Arelli; J. G. Shannon (Theoretical and Applied Genetics, 2006)

Role of the JAK-STAT pathway in protection of hydrogen peroxide preconditioning against apoptosis induced by oxidative stress in PC12 cells - H. M. Yu; J. L. Zhi; Y. Cui; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Curcumin protects PC12 cells against 1-methyl-4-phenylpyridinium ion-induced apoptosis by bcl-2-mitochondria-ROS-iNOS pathway - J. Chen; X. Q. Tang; J. L. Zhi; Y. Cui; H. M. Yu; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Length-dependent deactivation of ventricular trabeculae in the bivalve, Spisula solidissima - L. P. Collis; Y. Sun; R. B. Hill (Journal of Comparative Physiology B, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Survival of faecal coliforms and hygiene risks in soils treated with municipal sewage sludges - Y.H. Sun; Y.M. Luo; L.H. Wu; Z.G. Li; J. Song; P. Christie (Environmental Geochemistry and Health, 2006)

Sequence variability of the human cytomegalovirus UL141 Open Reading Frame in clinical strains - Y.-P. Ma; Q. Ruan; R. He; Y. Qi; Z.-R. Sun; Y.-H. Ji; Y.-J. Huang; Q. Liu; S.-R. Chen; J.-D. Wang (Archives of Virology, 2006)

Leaching of Copper from an Industrial Sludge Applied on a Soil Column - J. Xu; S. Dai; X. Han; S. Sun; P. Zhang (Bulletin of Environmental Contamination and Toxicology, 2006)

Verapamil modulates LPS-induced cytokine production via inhibition of NF-kappa B activation in the liver - G. Li; X. P. Qi; X. Y. Wu; F. K. Liu; Z. Xu; C. Chen; X. D. Yang; Z. Sun; J. S. Li (Inflammation Research, 2006)

Combination of temporal gravity variations resulting from superconducting gravimeter (SG) recordings, GRACE satellite observations and global hydrology models - J. Neumeyer; F. Barthelmes; O. Dierks; F. Flechtner; M. Harnisch; G. Harnisch; J. Hinderer; Y. Imanishi; C. Kroner; B. Meurers; S. Petrovic; Ch. Reigber; et al. (Journal of Geodesy, 2006)

Evolution of Dystaenia takesimana (Apiaceae), endemic to Ullung Island, Korea - M. Pfosser; G. Jakubowsky; P. M. Schlüter; T. Fer; H. Kato; T. F. Stuessy; B.-Y. Sun (Plant Systematics and Evolution, 2005)

Wavelet filter analysis of local atmospheric pressure effects on gravity variations - X.-G Hu; L.-T Liu; J. Hinderer; H.-P Sun (Journal of Geodesy, 2005)

Rhizosphere Competent Pseudomonas aeruginosa GRC1 Produces Characteristic Siderophore and Enhances Growth of Indian Mustard (Brassica campestris) - Piyush Pandey; Sun C. Kang; Chandra P. Gupta; Dinesh K. Maheshwari (Current Microbiology, 2005)

Adsorption of Bisphenol A on Sediments in the Yellow River - W. L. Sun; J. R. Ni; K. C. O'Brien; P. P. Hao; L. Y. Sun (Water, Air, & Soil Pollution, 2005)

Sustained Vascular Endothelial Growth Factor Delivery Enhances Angiogenesis and Perfusion in Ischemic Hind Limb - Qinghua Sun; Ruth R. Chen; Yuechun Shen; David J. Mooney; Sanjay Rajagopalan; P. Michael Grossman (Pharmaceutical Research, 2005)

Biososteric Replacement in the Design and Synthesis of Ligands for Nicotinic Acetylcholine Receptors - Weilin Sun; Michael P. Blanton; Jerome L. Gabriel; Daniel J. Canney (Medicinal Chemistry Research, 2005)

Development of an automated protein-tyrosine phosphatase 1B inhibition assay and the screening of putative insulin-enhancing vanadium(IV) and zinc(II) complexes - Andre P. Seale; Lucia A. de Jesus; Se-Yeon Kim; Yeon-Hong Choi; H. B. Lim; Cheong-Soo Hwang; Yang-Sun Kim (Biotechnology Letters, 2005)

Characterization of two genes encoding leucine-rich repeat-containing proteins in grass carp Ctenopharyngodon idellus - M. X. Chang; P. Nie; H. X. Xie; B. J. Sun; Q. Gao (Immunogenetics, 2005)

The TATGARAT Box of the HSV-1 ICP27 Gene is Essential for Immediate Early Expression but not Critical for Efficient Replication in vitro or in vivo - Aixu Sun; G. Devi-Rao; M. Rice; L. Gary; D. Bloom; R. Sandri-Goldin; P. Wagner (Virus Genes, 2004)

Characterization of two membrane‐associated protease genes obtained from screening out‐membrane protein genes of Flavobacterium columnare G 4 - H X Xie; P Nie; B J Sun (Journal of Fish Diseases, 2004)
In order to identify genes encoding the outer membrane proteins (OMPs) of the myxobacter Flavobacterium columnare G 4 , the expression library of the bacterium was screened by using rabbit antisera developed against its OMPs. Positive colonies of Escherichia coli M15 containing fragments encoding the bacterial OMPs were selected for cloning the relevant genes by genomic walking methods. Two genes encoding a membrane‐associated zinc metalloprotease and prolyl oligopeptidase are reported in this paper. The membrane‐associated zinc metalloprotease gene ( map ) is 1800 bp in length, coding for 449 amino acids (aa). Despite the presence of a conserved motif HEXXH for all metalloproteases, the special HEXXH ∼ 32 aa ∼ E motif of the F. columnare G 4 Map and its low level of identity with other reported zinc‐containing metalloproteases may imply that the membrane‐associated zinc metalloprotease of F. columnare G 4 represents a new family of zincins. The gene encoding prolyl oligopeptidase (Pop), a serine proteinase, is 2352 bp in length, coding for 649 aa. Sequence homology analysis revealed that the Pop is also novel as it has F. columnare .

A study of gravity variations caused by polar motion using superconducting gravimeter data from the GGP network - J.-Q. Xu; H.-P. Sun; X.-F. Yang (Journal of Geodesy, 2004)

Transporter and ion channel gene expression after caco-2 cell differentiation using 2 different microarray technologies - Christopher P. Landowski; Pascale Anderle; Duxin Sun; Wolfgang Sadee; Gordon L. Amidon (The AAPS Journal, 2004)

The Adsorption of Lead and Copper from Aqueous Solution on Modified Peat–Resin Particles - Q.Y. Sun; P. Lu; L.Z. Yang (Environmental Geochemistry and Health, 2004)

Residues of Hexachlorocyclohexane Isomers and Their Distribution Characteristics in Soils in the Tianjin Area, China - Z. M. Gong; F. L. Xu; R. Dawson; J. Cao; W. X. Liu; B. G. Li; W. R. Shen; W. J. Zhang; B. P. Qin; R. Sun; S. Tao (Archives of Environmental Contamination and Toxicology, 2004)

Inheritance of plant regeneration from maize (Zea mays L.) shoot meristem cultures derived from germinated seeds and the identification of associated RAPD and SSR markers - W. Li; G. Sun; J. Liu; P. Masilamany; J. H. Taylor; W. Yan; K. J. Kasha; K. P. Pauls (Theoretical and Applied Genetics, 2004)

Atmospheric Disturbances that Generate Intermittent Turbulence in Nocturnal Boundary Layers - Jielun Sun; Donald H. Lenschow; Sean P. Burns; Robert M. Banta; Rob K. Newsom; Richard Coulter; Stephen Frasier; Turker Ince; Carmen Nappo; Ben B. Balsley; Michael Jensen; Larry Mahrt; et al. (Boundary-Layer Meteorology, 2004)

Applications of combined DNA microarray and chromosome sorting technologies - S. M. Gribble; H. Fiegler; D. C. Burford; E. Prigmore; F. Yang; P. Carr; B. L. Ng; T. Sun; E. S. Kamberov; V. L. Makarov; J. P. Langmore; N. P. Carter (Chromosome Research, 2004)

1,2,4-Trichlorobenzene Induction of Chromosomal Aberrations and Cell Division of Root-Tip Cells in Vicia faba Seedlings - W. Liu; Q.-X. Zhou; P.-J. Li; T.-H. Sun; Y.-S. Yang; X.-Z. Xiong (Bulletin of Environmental Contamination and Toxicology, 2003)

Abundance of Calanus sinicus across the tidal front in the Yellow Sea, China - G. M. Liu; S. Sun; H. Wang; Y. Zhang; B. Yang; P. Ji (Fisheries Oceanography, 2003)
The abundance of Calanus sinicus eggs, nauplii, copepodites and adults and chlorophyll a (Chl‐ a ) concentration were studied across tidal fronts in October 2000, and May and June 2001 in the Yellow Sea, China. The aim of the study was to evaluate the role of tidal fronts in the ecology of C. sinicus . The hydrographic tidal fronts were identified by the horizontal temperature gradient in the bottom layer and the temperature profiles across the fronts. The survey results showed that the concentration of Chl‐ a was high in the vicinity of the fronts, particularly in spring and early summer. The abundance of C. sinicus eggs and nauplii was usually higher in the tidal fronts than in the adjacent areas. In May and June 2001, the abundance of copepodites and adults of C. sinicus peaked in the tidal front. In June 2001 and October 2000, many copepodites and adults were found in stratified region.

Long-term cattle manure application in soil. II. Effect on soil microbial populations and community structure - J. A. Parham; S. P. Deng; H. N. Da; H. Y. Sun; W. R. Raun (Biology and Fertility of Soils, 2003)

EGF Stimulates Growth by Enhancing Capacitative Calcium Entry in Corneal Epithelial Cells - H. Yang; X. Sun; Z. Wang; G. Ning; F. Zhang; J. Kong; L. Lu; P. S. Reinach (The Journal of Membrane Biology, 2003)

Changes in carbon storage and fluxes in a chronosequence of ponderosa pine - B. E. LAW; O. J. SUN; J. CAMPBELL; S. VAN TUYL; P. E. THORNTON (Global Change Biology, 2003)
Forest development following stand‐replacing disturbance influences a variety of ecosystem processes including carbon exchange with the atmosphere. On a series of ponderosa pine ( Pinius ponderosa var. Laws.) stands ranging from 9 to> 300 years in central Oregon, USA, we used biological measurements to estimate carbon storage in vegetation and soil pools, net primary productivity (NPP) and net ecosystem productivity (NEP) to examine variation with stand age. Measurements were made on plots representing four age classes with three replications: initiation ( I , 9–23 years), young ( Y , 56–89 years), mature ( M , 95–106 years), and old ( O , 190–316 years) stands typical of the forest type in the region. Net ecosystem productivity was lowest in the I stands (−124 g C m −2 yr −1 ), moderate in Y stands (118 g C m −2 yr −1 ), highest in M stands (170 g C m −2 yr −1 ), and low in the O stands (35 g C m −2 yr −1 ). Net primary productivity followed similar trends, but did not decline as much in the O stands. The ratio of fine root to foliage carbon was highest in the I stands, which is likely necessary for establishment in the semiarid environment, where forests are subject to drought during the growing season (300–800 mm precipitation per year). Carbon storage in live mass was the highest in the O stands (mean 17.6 kg C m −2 ). Total ecosystem carbon storage and the fraction of ecosystem carbon in aboveground wood mass increased rapidly until 150–200 years, and did not decline in older stands. Forest inventory data on 950 ponderosa pine plots in Oregon show that the greatest proportion of plots exist in stands ∼ 100 years old, indicating that a majority of stands are approaching maximum carbon storage and net carbon uptake. Our data suggests that NEP averages ∼ 70 g C m −2 year −1 for ponderosa pine forests in Oregon. About 85% of the total carbon storage in biomass on the survey plots exists in stands greater than 100 years, which has implications for managing forests for carbon sequestration. To investigate variation in carbon storage and fluxes with disturbance, simulation with process models requires a dynamic parameterization for biomass allocation that depends on stand age, and should include a representation of competition between multiple plant functional types for space, water, and nutrients.

Intermittent Turbulence Associated with a Density Current Passage in the Stable Boundary Layer - Jielun Sun; Sean P. Burns; Donald H. Lenschow; Robert Banta; Rob Newsom; Richard Coulter; Stephen Frasier; Turker Ince; Carmen Nappo; Joan Cuxart; William Blumen; Xuhui Lee; et al. (Boundary-Layer Meteorology, 2002)

Comparison of Human Duodenum and Caco-2 Gene Expression Profiles for 12,000 Gene Sequences Tags and Correlation with Permeability of 26 Drugs - Duxin Sun; Hans Lennernas; Lynda S. Welage; Jeffery L. Barnett; Christopher P. Landowski; David Foster; David Fleisher; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2002)

Adsorption of Paraquat onto Activated Bleaching Earth - W. T. Tsai; M. F. Hsieh; H. F. Sun; S. F. Chien; H. P. Chen (Bulletin of Environmental Contamination and Toxicology, 2002)

Pain model and fuzzy logic patient-controlled analgesia in shock-wave lithotripsy - J. -S. Shieh; L. -W. Chang; M. -S. Wang; Y. -P. Wang; Y. -P. Yang; W. -Z. Sun (Medical & Biological Engineering & Computing, 2002)

Preliminary genetic data on some Caribbean Artemia franciscana strains based on RAPD's - W. N. Camargo; P. Bossier; P. Sorgeloos; Y. Sun (Hydrobiologia, 2002)

Mapping quantitative trait loci for milling quality, protein content and color characteristics of rice using a recombinant inbred line population derived from an elite rice hybrid - Y. F. Tan; M. Sun; Y. Z. Xing; J. P. Hua; X. L. Sun; Q. F. Zhang; H. Corke (Theoretical and Applied Genetics, 2001)

A set of useful monocotyledon transformation vectors - S. Ahlandsberg; P. Sathish; C. Sun; C. Jansson (Biotechnology Letters, 2001)

Precise tidal gravity recorded with superconducting gravimeters at stations Wuhan (China) and Kyoto (Japan) - H.-P. Sun; S. Takemoto; H.-T. Hsu; T. Higashi; A. Mukai (Journal of Geodesy, 2001)

Comparative study of platinum‐group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei‐Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)
The Zambales Ophiolite Complex (ZOC), Philippines, includes two geochemically distinct, ophiolitic assemblages: the high‐Al chromitite‐bearing Coto Block and high‐Cr chromitite‐bearing Acoje Block. This paper reports a comparative platinum‐group element (PGE) study of these two blocks. The PGE data were obtained using Ni‐sulfide fire assay preconcentration combined with inductively coupled plasma mass spectrometry (ICP‐MS) measurement. Podiform chromitites in the Acoje Block have higher Cu, Ir, Ru and Rh contents than their equivalents in the Coto Block, although chromitites from both have similar Pt and Pd contents. The PGE mantle‐normalized patterns of dunites from the two blocks are also different: dunites from the Coto Block are depleted in Pt, whereas those from the Acoje Block have a relatively flat pattern. The data demonstrate that Coto and Acoje Blocks have different origins in terms of their source region and partial melting processes. This study implies that the ZOC is a paired ophiolite belt formed in an island arc and back‐arc basin environment.

Comparative study of platinum-group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei-Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)

Mössbauer, EPR, and MCD studies of the C9S and C42S variants of Clostridium pasteurianum rubredoxin and MCD studies of the wild-type protein - Sun Jae Yoo; Jacques Meyer; Catalina Achim; James Peterson; Michael P. Hendrich; E. Münck (JBIC Journal of Biological Inorganic Chemistry, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

The enzymes involved in synthesis and utilization of carbamylphosphate in the deep-sea tube worm Riftia pachyptila - V. Simon; C. Purcarea; K. Sun; J. Joseph; G. Frebourg; J.-P. Lechaire; F. Gaill; G. Hervé (Marine Biology, 2000)

Selenoprotein W accumulates primarily in primate skeletal muscle, heart, brain and tongue - Q-P Gu; Y. Sun; L.W. Ream; P.D. Whanger (Molecular and Cellular Biochemistry, 2000)

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

Analyses of isoamylase gene activity in wild-type barley indicate its involvement in starch synthesis - Chuanxin Sun; P. Sathish; Staffan Ahlandsberg; Christer Jansson (Plant Molecular Biology, 1999)

Isolation, Characterization, and Stability of Positional Isomers of Mono-PEGylated Salmon Calcitonins - Kang Choon Lee; Seung Cheol Moon; Myung Ok Park; Jung Tae Lee; Dong Hee Na; Sun Dong Yoo; Hye Suk Lee; Patrick P. DeLuca (Pharmaceutical Research, 1999)

Regulation of cell survival in CD95-induced T cell apoptosis: role of NF-κB/Rel transcription factors - A. Lamberti; M. F. Romano; V. Agosti; C. Garbi; S.-C. Sun; H.M. Bond; P. Bonelli; M. C. Turco; S. Venuta (Apoptosis, 1999)

Effects of phorbol esters on excitation-contraction coupling and protein kinase C activity of frog twitch muscle fibers - X. H. Zhang; J. H. Sun; P. H. Zhu (Pflügers Archiv - European Journal of Physiology, 1999)

Modeling Microbial Transport and Biodegradation in a Dual-porosity System - Y. Sun; J. N. petersen; J. Bear; T. P. Clement; B. S. Hooker (Transport in Porous Media, 1999)

Molecular Identification of a Murine Ubiquitin/60S Ribosomal Fusion Protein and Expression Study in Mouse Kidney - Lin Sun; Rudolf P. Wuthrich (Biochemical Genetics, 1999)

Interpretation of the tidal residuals during the 11 July 1991 total solar eclipse - B. Ducarme; H.-P. Sun; N. d'Oreye; M. Van Ruymbeke; J. Mena Jara (Journal of Geodesy, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Corticofugal regulation of auditory sensitivity in the bat inferior colliculus - P. H.-S. Jen; Q. C. Chen; X. D. Sun (Journal of Comparative Physiology A, 1998)

Geology, geochemistry and sulfur isotope composition of the Late Proterozoic Jingtieshan (Superior-type) hematite-jasper-barite iron ore deposits associated with stratabound Cu mineralization in the Gansu Province, China - H. Sun; J. Wu; P. Yu; J. Li (Mineralium Deposita, 1998)

Pollen‐based biome reconstructions for China at 0 and 6000 years - Ge Yu; I. Colin Prentice; Sandy P. Harrison; Xiangjun Sun (Journal of Biogeography, 1998)
Biomization provides an objective and robust method of assigning pollen spectra to biomes so that pollen data can be mapped and compared directly with the output of biomgeographic models. We have tested the applicability of this procedure, originally developed for Europe, to assign modern surface samples from China to biomes. The procedure successfully delineated the major vegetation types of China. When the same procedure was applied to fossil pollen samples for 6000 years ago, the reconstructions showed systematic differences from present, consistent with previous interpretations of vegetation changes since the mid‐Holocene. In eastern China, the forest zones were systematically shifted northwards, such that cool mixed forests displaced taiga in northeastern China, while broad‐leaved evergreen forest extended c . 300 km and temperate deciduous forest c . 500–600 km beyond their present northern limits. In northwestern China, the area of desert and steppe vegetation was reduced compared to present. On the Tibetan Plateau, forest vegetation extended to higher elevations than today and the area of tundra was reduced. These shifts in biome distributions imply significant changes in climate since 6000 years ago that can be interpreted qualitatively as a response to orbital forcing and its secondary effects on the Asian monsoon.

On some problems of the downward continuation of the 5 ′ ×5 ′ mean Helmert gravity disturbance - W. Sun; P. Vaníček (Journal of Geodesy, 1998)

Differentiation and classification of parental lines and favorable genic interactions affecting F1 fertility in distant crosses of rice (Oryza sativa L.) - R. H. Li; C. G. Xue; L. P. Yuan; Y. Q. He; C. Q. Sun; S. B. Yu; X. H. Li; X. K. Wang (Theoretical and Applied Genetics, 1998)

Quantification of bacteriophages ofBacteroides fragilis in environmental water samples of Seine River - Z. P. Sun; Y. Levi; L. Kiene; N. Dumoutier; F. Lucena (Water, Air, & Soil Pollution, 1997)

QUANTIFICATION OF BACTERIOPHAGES OF BACTEROIDES FRAGILIS IN ENVIRONMENTAL WATER SAMPLES OF SEINE RIVER - Z. P. SUN; Y. LEVI; L. KIENE; N. DUMOUTIER; F. LUCENA (Water, Air, & Soil Pollution, 1997)

Production, disinfection and evaluation for aquaculture applications of rotifer resting eggs from Bohai Bay, P.R. of China - Ph. Dhert; K. Schoeters; P. Vermeulen; J. Sun; S. Gao; Z. Shang; X. Naihong; H. Van Duffel; P. Sorgeloos (Aquaculture International, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Nonlinear phenomenon of interfacial polarization immittance of a Pt electrode - M. Moussavi; H. H. Sun; H. P. Schwan; A. Richter (Annals of Biomedical Engineering, 1990)